Low-VOC multifunctional additives for improving the properties of waterborne polymeric films
Patent Information
- Application Number
- JP2021560216
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-05
- Filing Date
- 2020-04-03
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-04-03
AI Technical Summary
【0041】 第十四の実施態様においては、本発明は、金属への直接コーティング物における、湿時接着性、硬度の改良、腐食(フラッシュ錆)抵抗性、ブロック抵抗性、吸塵抵抗性、及びスクラブ抵抗性の多機能向上作用を与えるための、水性コーティングの中に組み入れた、安息香酸ナトリウム、ジベンゾエート、及びベンジルアルコールの混合物を目的としている。
Smart Images

Figure 0007644021000016 
Figure 0007644021000017 
Figure 0007644021000018
Abstract
Description
[Technical field]
[0001] The present invention is directed to low volatile organic compounds (VOC) multifunctional additives for aqueous polymeric film-forming compositions, which, in addition to coalescent function, provide improved properties to films formed therefrom, such as hardness, scrub resistance, block resistance, and flash rust resistance, among other properties. The present invention is also directed to a method for increasing and improving the hardness and scrub resistance, among other properties, of aqueous polymeric film-forming compositions, by using the multifunctional additive blends of the present invention. The blends include traditional low volatility coalescent agents in combination with high volatility components, some of which are not known or previously used as coalescent agents. It has been discovered that certain combinations of high volatility components and traditional low volatility components act synergistically to improve the properties of aqueous polymeric films, while significantly minimizing the VOC content. The present invention is also directed to a method for improving the properties of aqueous coatings using the low VOC multifunctional additive blends of the present invention. [Background technology]
[0002] Various coating applications may require good surface hardness as an important property of the film formed by the coating. Coating hardness is an important property for wear-resistant coatings and hardfacing of tool parts, as well as for thermal and water barrier coatings. The development of hardness in water-based coatings is crucial for block resistance and dirt pick-up, prevents abrasion, provides resistance to indentation and scratching, and improves barrier properties, among other reasons known to those skilled in the art. Scrub resistance is also highly desirable in coatings, especially for coating surfaces that require repeated cleaning. Some of the blends of the present invention, as described herein, have provided greatly improved scrub resistance in some coating systems.
[0003] Several methods are known to increase hardness. For example, the hardness of a coating can be increased by using various fillers, such as mineral additives, clays, and other thickeners. Some polymer compositions contain a "high solids" content, which may also contribute to hardness. It is also possible to select binders with a certain degree of hardness or particle size. Coating properties can also be altered by using blends of binders or by varying the presence of certain polymers in the binder. Improved hardness may also be obtained by varying the thickness of the coating. Other methods to improve hardness, along with other properties, include the use of core / shell, grading the composition, and including crosslinking groups in the composition. Still other methods are known to those skilled in the art. Despite the success of these methods to improve hardness and other properties, efforts continue to develop methods and additives that, in part, further improve properties and add additional functionality to the coating.
[0004] In addition to hardness and improved scrub resistance, corrosion resistance is required in some coatings and other water-based polymer compositions. For example, in latex direct-to-metal coatings, corrosion protection, specifically flash rust resistance, is especially required due to the nature of the coating being a water-based system. When applied to a metal surface, water-based coating formulations contain ionic electrolytes, water, and oxygen, all of which are necessary for corrosion to occur. As a result, flash rust can form on the metal surface. It is known that organic acids and salts, such as benzoic acid and sodium benzoate, provide corrosion protection through anodic protection by adsorbing metal ions and preventing them from dissolving in an aqueous environment. Generally, these organic acids and salts are added separately throughout the formulation process, however, it has been found that it is very difficult to incorporate benzoic acid into water-based polymer systems due to its low water solubility.
[0005] Although there is a continuous effort to improve the properties of coatings, consumers and environmental regulators continue to pressure for lower volatile organic compound ("VOC") content in coatings. VOCs are carbon-containing compounds that can easily volatilize or volatilize into the atmosphere and react with other elements or compounds. VOCs are of particular concern in the paint and coatings industry with respect to the manufacture and use of products that contain VOCs. The use of VOCs in the manufacture of paints and coatings can, under certain circumstances, lead to poor air quality in plants and exposure of workers to harmful chemicals. Similarly, applicators and other users of VOC-containing paints and coatings who are constantly exposed to harmful VOC vapors can face health problems. People exposed to VOCs can face numerous health problems, including but not limited to several types of headaches, cancer, damage to brain function, kidney and liver failure, breathing difficulties, and other health problems.
[0006] Paints and coatings with high VOC content are also considered hazardous to the environment. They are the second largest source of VOC emissions into the atmosphere after automobiles, emitting roughly 11 billion pounds annually. Regulations have been put in place to protect manufacturing workers and end users. Consumers are also demanding safer alternatives. While formulators can reduce or replace the most volatile ingredients used in coatings, which can reduce VOC concerns to some extent, this can result in performance loss. Desirably, paints or coatings with low VOC content should perform as well as paints or coatings with higher VOC content. Towards this goal, raw material suppliers are continually challenged to develop new, lower VOC products for use in paints and coatings that keep the VOC content lower but do not compromise performance.
[0007] A volatile, but usually essential, ingredient that has been used historically in coating compositions is the coalescent, or coalescent agent. Coalescents allow coating formulators to use well-known latex emulsions that are low cost and do not require coalescents. gThis allows for superior performance to be achieved, comparable to conventional polymer-based coatings. The coalescent agent facilitates film formation by softening the dispersed polymers and causing them to coalesce or form a continuous film. The coalescent agent then evaporates out of the film, either partially or fully, allowing the film to regain its original physical properties. The coalescent agent is selected to improve the paint / coating film properties, such as hardness, gloss, scrub resistance, and block resistance. The coalescent agent is also selected based on various performance criteria, including but not limited to volatility, miscibility, stability, compatibility, ease of use, and cost. Traditional coalescent agents are highly volatile and can significantly contribute to the VOC content of the paint or coating.
[0008] Coalescent agents are known to those skilled in the art. The industry standard, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (TXMB) (available from Eastman Chemical as Eastman Texanol™), is widely used despite the fact that it is 100% volatile according to the EPA 24 ASTM D2369 test method. Other coalescent agents include glycol ethers, such as diethylene glycol monomethyl ether (DEGME), butyl cellosolve (ethylene glycol monobutyl ether), butyl Carbitol™ (diethylene glycol monobutyl ether), and dipropylene glycol n-butyl ether (DPnB), which are also highly volatile components used as coalescents or coalescing solvents. Highly volatile coalescent agents contribute VOCs starting from the coalescing phase and continuing for a long period thereafter. This, in turn, can manifest itself as an unpleasant odor and affect the air around the film.
[0009] Because of these problems, there is a trend toward the development and use of less volatile, more permanent coalescents for coatings and other film-forming compositions. For example, Optifilm™ Enhancer 400 (or OE-400) (available from Eastman Chemical), a newer, lower VOC coalescent that has become the industry benchmark for lower VOC content coalescents, is identified in a Safety Data Sheet as triethylene glycol bis(ethylhexanoate-2), also known as triethylene glycol dioctanoate (TEGDO), available commercially from a number of suppliers. Another useful low-VOC coalescent is COASOL™ (Dow), which is a mixture of purified di-isobutyl esters of adipic, glutaric, and succinic acids in specific ratios that are said to be characterized by low odor and low vapor pressure. Still other useful low-VOC coalescents include citrates and other adipates.
[0010] In addition, plasticizers are known as excellent coalescent agents for latex paints and other coatings, being significantly less volatile than traditional coalescent agents. In some coating applications, plasticizers are also used for their plasticizing function in coatings, softening harder base polymers to make them more flexible and less brittle. Plasticizers are also known to improve other performance characteristics of paints, such as mud cracking, wet edges, and open time.
[0011] Phthalate plasticizers, such as di-n-butyl phthalate (DBP), diisobutyl phthalate (DIBP), or butyl benzyl phthalate (BBP), have high T gThey have traditionally been used in the coatings industry when true plasticizers are needed, such as when polymers with a low glass transition temperature (Tg) are employed in one application or another. DBP and DIBP have a lower VOC content than traditional coalescents, but are still somewhat volatile, whereas BBP has a very low VOC content. However, apart from VOC content, the use of phthalate esters has some drawbacks, because the use of DBP and BBP is subject to restrictions, especially in relation to regulations.
[0012] Dibenzoates are non-phthalates and do not have the same limitations and health concerns as phthalates. Traditional dibenzoates used as coalescents include 1,2-propylene glycol dibenzoate (PGDB), dipropylene glycol dibenzoate (DPGDB), and blends of diethylene glycol dibenzoate (DEGDB) with DPGDB and / or PGDB. Commercially available examples of benzoates include, but are not limited to, K-FLEX® DP (DPGDB), K-FLEX® 500 (DEGDB / DPGDB blend), K-FLEX® 850S (new grade DEGDB / DPGDB blend), and K-FLEX® 975P (new triple blend including DEGDB / DPGDB / 1,2-PGDB).
[0013] Dibenzoate glycol esters have been used extensively as plasticizers and coalescent "film-forming" aids for many years. The benefits of using certain dibenzoates in coatings are well known and include: low vapor pressure (10 -6 ~10 -8mmHg range, resulting in low VOC content), suitable solubility parameters for applications with polar polymers such as polyvinyl chloride (PVC) and acrylates, biodegradability, and safety for food contact applications in adhesives and coatings. The utility of dibenzoates as coalescents is already well established in architectural coatings for both interior and exterior applications. Their performance benefits in architectural coatings include increased solids volume, gloss, and scrub resistance.
[0014] Monobenzoate esters known to be useful as coalescents include isodecyl benzoate (IDB), isononyl benzoate (INB), and 2-ethylhexyl benzoate (EHB). For example, isodecyl benzoate is described in U.S. Pat. No. 5,399,633 (Arendt) as a useful coalescent for paint compositions. The use of 2-ethylhexyl benzoate in blends with DEGDB and diethylene glycol monobenzoate is described in U.S. Pat. No. 5,399,633 (Arendt et.al.). The use of isononyl esters of benzoic acid as film-formers in compositions such as emulsions, mortars, gypsums, adhesives, and varnishes is described in U.S. Pat. No. 5,399,633 (Grass et.al.). Phenylpropyl benzoate has also been found to be an excellent film-former for use in various coatings.
[0015] Other plasticizers useful in coatings to enable proper film formation and improve film properties in selected polymer systems include: non-phthalate 1,2-cyclohexanedicarboxylate esters such as diisononyl-1,2-cyclohexanedicarboxylate (available from BASF as Hexamoll® DINCH®).
[0016] Plasticizers are generally useful coalescents for water-based systems based on their low VOC contribution, but this same "low VOC contribution" also means that they have longer retention, i.e., they are less volatile and therefore slower to exit the film, than other traditional, higher VOC coalescents. In some cases, the retention of plasticizers can be detrimental. Formulators have a strong concern that retention can adversely affect certain properties, such as dirt pickup, adhesion, and film hardness. In using plasticizers as coalescents, a balance must be struck between high retention (and therefore lower VOC) and good final film properties. Desirably, paints or coatings with low VOC content should perform as well as paints or coatings with higher VOC content. Towards this end, raw material suppliers continue to develop new, lower VOC products for use in paints and coatings and other film-forming compositions that minimize compromises in performance and improve the properties of the polymer film. [Prior art documents] [Patent documents]
[0017] [Patent Document 1] U.S. Pat. No. 5,236,987 [Patent Document 2] U.S. Patent No. 6,989,830 [Patent Document 3] U.S. Patent No. 7,638,568 Summary of the Invention [Problem to be solved by the invention]
[0018] There remains an unmet need for coalescents that have lower VOC content while meeting or improving important coating properties such as hardness, scrub resistance, block resistance, hardness development, and dirt pickup resistance beyond those achieved with traditional high volatility coalescents. In addition, improved corrosion (flash rust) resistance is needed for certain applications, especially in waterborne polymer systems.
[0019] Low VOC multifunctional additive blends have been developed that provide lower VOC content and good coalescence properties to coatings and other film-forming compositions, while actually improving other important performance properties compared to the use of conventional high-VOC or low-VOC coalescents alone. These low-VOC multifunctional additives of the present invention achieve improved hardness and scrub resistance, among other properties of waterborne polymer systems, in addition to coalescence properties, by blending both high-volatility and low-volatility compounds. Specifically, it has been found that by blending certain low-volatility coalescents, such as but not limited to dibenzoate, phthalate, terephthalate, citrate, and adipate plasticizers and other low- or zero-VOC coalescents with certain high-volatility components, unexpected improved hardness, block resistance, dirt pickup resistance, and scrub resistance are achieved in various coatings. The multifunctional additives of the present invention use known high VOC coalescent agents as well as other, previously unknown and not used as coalescent agents, highly volatile compounds. In some embodiments, the low VOC multifunctional additives of the present invention may further include anti-corrosion compounds to enhance the functionality provided by the additive.
[0020] It has further been found that organic acids, such as benzoic acid, can be incorporated into aqueous polymer systems in combination with the novel multifunctional additive of the present invention to improve corrosion resistance (flash rust resistance) in addition to achieving other property improvements. Benzoic acid is known to be insoluble in water and difficult to incorporate into aqueous polymer systems. However, it has been found that in the low VOC multifunctional additive of the present invention, benzoic acid is soluble to some extent, thus providing a novel method of incorporating organic acids, such as benzoic acid, into aqueous polymer systems. Organic salts, such as sodium benzoate, can be dissolved in water up to about 30% and can be added to aqueous coatings containing the low VOC multifunctional additive blend of the present invention to improve the flash rust resistance of the coating.
[0021] It is an object of the present invention to provide a coalescent agent for use in aqueous polymeric film forming compositions, including but not limited to coatings, by blending a low volatility component with a high volatility component to obtain a coating with lower VOC content, thereby improving the performance of the polymeric film.
[0022] It is a further object of the present invention to provide an aqueous coating having improved hardness and scrub resistance, among other properties, by blending a high volatility component with a low volatility component, than previously achieved using either conventional high volatility or low volatility coalescent agents alone.
[0023] It is yet another object of the present invention to provide a method for improving hardness and scrub resistance, among other properties, of waterborne polymer systems beyond those achieved using conventional high and low volatility coalescents by using a low VOC multifunctional additive comprising a blend of low and high volatility components.
[0024] Yet another object of the present invention is to improve the performance of aqueous polymeric film forming compositions by adding the multifunctional additive blend of the present invention for purposes including, but not limited to, improving hardness, hardness development, scrub resistance, corrosion (flash rust) resistance, dirt pickup resistance, and block resistance.
[0025] Yet another object of the present invention is to provide a vehicle or carrier for solutions / dispersions of pigments and colorants (stains, dyes) for addition to aqueous polymeric film-forming compositions, wherein the vehicle comprises the low VOC multifunctional additive of the present invention.
[0026] Still other objects of the present invention will be known to those of skill in the art based on the disclosure herein.
[0027] The present invention is directed to low VOC multifunctional additive compositions for use in waterborne coatings and other waterborne polymeric film-forming compositions which provide improved hardness and scrub resistance, hardness development, dirt pickup resistance, block resistance, corrosion (flash rust) resistance, among other properties, in addition to coalescence, compared to that achieved with conventional high or low volatility coalescents alone. The present invention is also directed to a method for improving the hardness and scrub resistance and other properties of waterborne coatings and other waterborne polymeric film-forming compositions over that achieved with conventional coalescents by adding the low VOC multifunctional additive compositions of the present invention. [Means for solving the problem]
[0028] In a first embodiment, the present invention is a low VOC multifunctional additive blend for use in waterborne coatings and other waterborne polymer film-forming applications, comprising a low volatility coalescent (coalescent) blended with a high volatility component comprising glycol ethers, TXMB, benzylamine, phenoxyethanol, phenylethanol, benzyl alcohol, benzyl benzoate, 3-phenylpropanol, 2-methyl-3-phenylpropanol, vanillin, or β-methylcinnamyl alcohol (cypriol).
[0029] In a second embodiment, the present invention is a low VOC multifunctional additive for use in waterborne coatings, where the additive includes a blend of known low volatility coalescents including benzoate esters, phthalates, terephthalates, 1,2-cyclohexanoate dicarboxylate esters, citrates, adipates, Optifilm™ Enhancer 400, TEGDO, or a mixture of purified di-isobutyl esters of adipic, glutaric, and succinic acids (Coasol™) with higher volatility components.
[0030] In a third embodiment, the present invention is a water-based coating comprising the low VOC multifunctional additive blend of the present invention.
[0031] In a fourth embodiment, the present invention is a water-based coating comprising a styrene-acrylic binder and the low VOC multifunctional additive blend of the present invention.
[0032] In a fifth embodiment, the present invention is a water-based coating comprising a vinyl acrylic binder and the multi-functional additive blend of the present invention.
[0033] In a sixth embodiment, the present invention is a water-based coating comprising a 100% acrylic binder and the low VOC multifunctional additive blend of the present invention.
[0034] In a seventh embodiment, the present invention is a waterborne coating comprising a vinyl acetate-ethylene binder and the low VOC multifunctional additive blend of the present invention.
[0035] In an eighth embodiment, the present invention is a water-based coating comprising VeoVa™ binder, a vinyl ester of versatic acid (available from Hexion), and the low VOC multi-functional additive blend of the present invention.
[0036] In a ninth embodiment, the present invention provides a method for improving the hardness, hardness development, block resistance, dirt pickup resistance, scrub resistance, wet adhesion, and corrosion (flash rust) resistance of waterborne coatings and other waterborne polymeric film-forming compositions comprising the step of adding during formulation of the waterborne coating or waterborne polymeric film-forming composition a low VOC multifunctional additive blend of the present invention.
[0037] In a tenth embodiment, the present invention is a method for incorporating benzoic acid, using a molar excess thereof, in the synthesis of a dibenzoate coalescent used in a low VOC multifunctional additive blend to improve the corrosion resistance and wet adhesion, among other properties, of direct-to-metal coatings.
[0038] In an eleventh embodiment, the present invention is a low VOC multifunctional additive comprising an acid excess dibenzoate as a low volatility component in combination with a high volatility component.
[0039] In a twelfth embodiment, the present invention is a method of combining an excess of an acid-dibenzoate with benzyl alcohol to make a low VOC anti-corrosion coalescent with multi-functional enhancements of wet adhesion, hardness improvement, corrosion resistance, block resistance, dirt pick-up resistance, and scrub resistance in direct-to-metal coatings.
[0040] In a thirteenth embodiment, the present invention is a method of dissolving benzoic acid, dibenzoate, and benzyl alcohol in one mixture with each other to make a low VOC anti-corrosion coalescent with multi-functional enhancement of wet adhesion, hardness improvement, corrosion resistance, block resistance, dirt pick-up resistance, and scrub resistance in direct-to-metal coatings.
[0041] In a fourteenth embodiment, the present invention is directed to a mixture of sodium benzoate, dibenzoate, and benzyl alcohol incorporated into an aqueous coating to provide multi-functional enhancements of wet adhesion, hardness improvement, corrosion (flash rust) resistance, block resistance, dirt pickup resistance, and scrub resistance in direct-to-metal coatings.
[0042] In a fifteenth embodiment, the present invention is directed to a carrier or dispersant for a colorant added to the aqueous film forming composition of the present invention comprising the low VOC multifunctional additive of the present invention.
[0043] Other embodiments will be apparent to those of skill in the art based on the disclosure herein. [Brief description of the drawings]
[0044] [Figure 1] FIG. 1 illustrates the improved scrub resistance performance (scrub cycles) achieved in a rigid styrene-acrylic resin (Encor 471) comparing the use of TXMB alone, K-FLEX® 975P alone, and a low-VOC multifunctional additive blend of the present invention (including a 70:30 blend of TXMB:K-FLEX® 975P). [Diagram 2] FIG. 1 illustrates the improved scrub resistance performance achieved in a styrene-acrylic resin (EPS 2533) comparing the use of TXMB alone, K-FLEX® 975P alone, and a low-VOC multifunctional additive blend of the present invention (including a 70:30 blend of TXMB to K-FLEX® 975P). [Diagram 3]FIG. 1 illustrates the improved scrub resistance performance achieved with a styrene acrylic resin (Acronal 296D) comparing the use of TXMB alone, K-FLEX® 975P alone, and a low-VOC multifunctional additive blend of the present invention (including a 10:90 blend of TXMB:K-FLEX® 975P). [Figure 4] FIG. 1 illustrates the improved scrub resistance performance achieved with 100% acrylic resin (Encor 626) comparing the use of TXMB alone, K-FLEX® 850S alone, and the low-VOC multifunctional additive blend of the present invention (comprising 10:90 TXMB:K-FLEX® 850S). [Diagram 5] FIG. 1 illustrates the improved scrub resistance performance achieved with a 100% acrylic resin (VSR 1050) comparing the use of TXMB alone, K-FLEX® 850S alone, and the low-VOC multifunctional additive blend of the present invention (comprising 10:90 TXMB:K-FLEX® 850S). [Figure 6] FIG. 1 illustrates the improved scrub resistance performance achieved in a vinyl acrylic resin (Encor 379G) comparing the use of TXMB alone, K-FLEX® 850S alone, and a low-VOC multifunctional additive blend of the present invention (comprising 80:20 TXMB:K-FLEX® 850S). [Figure 7a] FIG. 1 shows the flow and leveling results (ratings) achieved for Encor 471 Flat, Encor 471 Semi-Gloss, Encor 626 Flat, and Encor 626 Semi-Gloss samples comparing samples containing TXMB, OE-400, K-FLEX® 850S, and three inventive low-VOC multi-functional additive blends containing different ratios of benzyl alcohol and K-FLEX® 850S. [Figure 7b]FIG. 1 shows the flow and leveling results (ratings) achieved for Encor 471 flat, Encor 471 semi-gloss, Encor 626 flat, and Encor 626 semi-gloss samples comparing uncoalesced samples, as well as blends of TXMB, OE-400, K-FLEX® 850S, TXMB:OE-400 (1:1), and four inventive low-VOC multi-functional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and benzyl alcohol:OE-400 (1:1) blend). [Figure 8] FIG. 1 shows the scrub resistance results (percent increase in 85° gloss) achieved on flat samples of Encor 471 and Encor 626 comparing uncored samples and samples containing TXMB, OE-400, K-FLEX® 850S, and three of the inventive low-VOC multifunctional additive blends (X-3411, X-3412, and X-3413). [Figure 9a-9b] FIG. 1 shows Koenig hardness test results achieved using flat samples of Encor 471 and Encor 626 comparing uncored samples and samples containing three inventive low VOC multifunctional additive blends containing TXMB, OE-400, K-FLEX® 850S, and benzyl alcohol and K-FLEX® 850S in different ratios. [Fig. 9c-9d] FIG. 1 shows Koenig hardness results achieved with semi-gloss samples of Encor 471 and Encor 626 comparing uncored samples and samples of TXMB, OE-400, K-FLEX® 850S, a blend of TXMB:OE-400 (1:1), and four inventive low multi-function additive blends, including different ratios of benzyl alcohol and K-FLEX® 850S, and a 1:1 ratio of benzyl alcohol:OE-400. [Figure 9e]FIG. 1 shows Koenig hardness results achieved with samples of Encor 471 semi-gloss containing three inventive low VOC multifunctional additive blends in a 1:1 ratio: Cypriol:K-FLEX® 850S, 3-phenylpropanol:K-FLEX® 850S, and 2-methyl-3-phenylpropanol:K-FLEX® 850S. [Figure 10] FIG. 1 shows block resistance result ratings for Encor 471 flat and semi-gloss samples and Encor 626 flat and semi-gloss samples comparing (ambient temperature) uncored samples and samples of TXMB, K-FLEX® 850S, TXMB:OE-400 (1:1), and four inventive low-VOC multifunctional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and a blend of benzyl alcohol:OE-400 (1:1)). [Figure 11] FIG. 1 shows block resistance result ratings for Encor 471 flat and semi-gloss samples and Encor 626 flat and semi-gloss samples comparing (50° C.) uncored samples and samples of TXMB, K-FLEX® 850S, TXMB:OE-400 (1:1), and four inventive low-VOC multifunctional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and a blend of benzyl alcohol:OE-400 (1:1)). [Figure 12a] 1 is a photographic image showing low temperature coalescence results for Encor 471 Flat (10 mil) comparing samples containing three inventive low VOC multifunctional additive blends containing TXMB, OE-400, K-FLEX® 850S, and different ratios of benzyl alcohol and K-FLEX® 850S. [Figure 12b]FIG. 1 shows low temperature coalescence results (ratings) achieved for flat and semi-gloss samples of Encor 471 and Encor 626 comparing uncoalesced samples and samples of blends of TXMB, OE-400, K-FLEX® 850S, TXMB:OE-400 (1:1), and four inventive low VOC multifunctional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and benzyl alcohol:OE-400 (1:1)). [Figures 13a-13e] Contour plot showing the log reduction over time (days) for the following microorganisms in soy broth: A. brasiliensis (filamentous fungus), P. aeruginosa (gram-negative), E. coli (gram-negative), S. aureus (gram-positive), and C. albicans (yeast) for concentrations of 3-phenylpropanol ranging from 0.25% to 2.5% by weight. [Figure 14] FIG. 1 shows the Stormer viscosity (KU) results achieved for Encor 471 and Encor 626 flat and semi-gloss samples comparing uncoalesced samples and blends of TXMB, OE-400, K-FLEX® 850S, TXMB:OE-400 (1:1), and samples of four inventive low VOC multifunctional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and benzyl alcohol:OE-400 (1:1)). [Figure 15] FIG. 1 shows brightness ratio results achieved for Encor 471 and Encor 626 flat and semi-gloss samples comparing uncored samples and blends of TXMB, OE-400, K-FLEX® 850S, TXMB:OE-400 (1:1), and samples of four inventive low-VOC multifunctional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and benzyl alcohol:OE-400 (1:1)). [Figure 16-18] FIG. 1 shows gloss results achieved at angles of 20°, 60°, and 85° comparing uncored samples, as well as blends of TXMB, OE-400, K-FLEX® 850S, TXMB:OE-400 (1:1), and four inventive low VOC multifunctional additive blends (containing different ratios of benzyl alcohol and K-FLEX® 850S, and benzyl alcohol:OE-400 (1:1)) for flat and semi-gloss samples of Encor 471 and Encor 626, respectively. [Figure 19] FIG. 1 shows dirt pickup resistance results (percentage difference in reflectance) achieved for Encor 471 and Encor 626 flat and semi-gloss samples comparing uncored samples and blends of TXMB, OE-400, K-FLEX® 850S, TXMB:OE-400 (1:1), and samples of four inventive low VOC multifunctional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and benzyl alcohol:OE-400 (1:1)). [Figure 20] FIG. 1 shows print resistance results (rankings) achieved for Encor 471 and Encor 626 flat and semi-gloss samples comparing uncored samples and samples of TXMB, OE-400, K-FLEX® 850S, a blend of TXMB:OE-400 (1:1), and four inventive low-VOC multifunctional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and benzyl alcohol:OE-400 (1:1)). [Figure 21a-21b]FIG. 1 shows initial and final scrub resistance results (number of cycles) for Encor 471 and Encor 626 flat and semi-gloss samples, respectively, comparing uncored samples and samples of TXMB, OE-400, K-FLEX® 850S, a blend of TXMB:OE-400 (1:1), and four inventive low-VOC multifunctional additive blends (containing different ratios of benzyl alcohol and K-FLEX® 850S, and a blend of benzyl alcohol:OE-400 (1:1)). [Figure 22] FIG. 1 shows the dry adhesion results (ratings) achieved for flat and semi-gloss samples of Encor 471 and Encor 626 comparing uncored samples and samples of blends of TXMB, OE-400, K-FLEX® 850S, TXMB:OE-400 (1:1), and four inventive low-VOC multifunctional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and benzyl alcohol:OE-400 (1:1)). [Figure 23] FIG. 1 shows the dry time results (hours:min) achieved for Encor 471 and Encor 626 flat and semi-gloss samples comparing uncoalesced samples and blends of TXMB, OE-400, K-FLEX® 850S, TXMB:OE-400 (1:1), and samples of four inventive low-VOC multifunctional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and benzyl alcohol:OE-400 (1:1)). [Figure 24-25]FIG. 1 shows mud cracking results (w / o cracking, max mils) achieved from 14 to 60 mils at ambient temperature and 40° F. for flat and semi-gloss samples of Encor 471 and Encor 626 comparing uncoalesced samples and blends of TXMB, OE-400, K-FLEX® 850S, TXMB:OE-400 (1:1), and samples of four inventive low VOC multifunctional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and benzyl alcohol:OE-400 (1:1)). [Figure 26] FIG. 1 shows the open time results (hours:min) achieved for Encor 471 and Encor 626 flat and semi-gloss samples comparing uncoalesced samples and blends of TXMB, OE-400, K-FLEX® 850S, TXMB:OE-400 (1:1), and samples of four inventive low VOC multifunctional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and benzyl alcohol:OE-400 (1:1)). [Figure 27] FIG. 1 shows wet edge results (time:min) achieved for flat and semi-gloss samples of Encor 471 and Encor 626 comparing uncored samples and blends of TXMB, OE-400, K-FLEX® 850S, TXMB:OE-400 (1:1), and samples of four inventive low VOC multifunctional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and benzyl alcohol:OE-400 (1:1)). [Figure 28]FIG. 1 shows sag resistance results (rankings) achieved for Encor 471 and Encor 626 flat and semi-gloss samples comparing uncored samples, as well as blends of TXMB, OE-400, K-FLEX® 850S, TXMB:OE-400 (1:1), and four inventive low VOC multifunctional additive blends (containing different ratios of benzyl alcohol and K-FLEX® 850S, and benzyl alcohol:OE-400 (1:1) samples). [Fig. 29a-h] FIG. 1 shows washability results (ΔE*) achieved for flat and semi-gloss samples of Encor 471 and Encor 626 on a variety of aqueous and oily soils comparing uncoalesced samples, as well as blends of TXMB, OE-400, K-FLEX® 850S, TXMB:OE-400 (1:1), and samples of four inventive low-VOC multifunctional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and benzyl alcohol:OE-400 (1:1)). [Diagram 30] FIG. 1 shows washability results (ΔE*) achieved for Encor 471 and Encor 626 flat and semi-gloss samples against permanent marker comparing uncoalesced samples, as well as blends of TXMB, OE-400, K-FLEX® 850S, TXMB:OE-400 (1:1), and samples of four inventive low VOC multi-functional additive blends (benzyl alcohol and K-FLEX® 850S in different ratios, and benzyl alcohol:OE-400 (1:1)). [Diagram 31]FIG. 2 shows the calculated VOC contribution (g / L) for various paint binders (Encor 471, EPS2533, Acronal 296D, Encor 626, VSR-1050, and Encor379G) comparing the VOC calculated per binder for TXMB, K-FLEX® 850S, K-FLEX® 975P, and two inventive low-VOC multifunctional additive blends containing TXMB and K-FLEX® 850S or 975P (depending on the binder) (see Example 21). [Diagram 32] FIG. 1 shows the initial and final scrub resistance results (number of scrub cycles) achieved with a styrene acrylic binder (Encor 471) comparing TXMB, OE-400, K-FLEX® 975P, and two inventive low-VOC multifunctional additive blends including TXMB:K-FLEX® 975P in ratios of (70:30) and (30:70). [Diagram 33] FIG. 1 shows the initial and final scrub resistance results (number of scrub cycles) achieved with another styrene acrylic binder (EPS 2533) comparing TXMB, OE-400, K-FLEX® 975P, and two inventive low VOC multifunctional additive blends containing TXMB:K-FLEX® 975P in ratios of (55:45) and (30:70). [Diagram 34] FIG. 1 shows the initial and final scrub resistance results (number of scrub cycles) achieved with yet another styrene acrylic binder (Acronal 296D) comparing TXMB, OE-400, K-FLEX® 975P, and two inventive low VOC multifunctional additive blends including TXMB:K-FLEX® 975P in ratios of (90:10) and (10:90). [Diagram 35]FIG. 1 shows the initial and final scrub resistance results (number of scrub cycles) achieved in a 100% acrylic binder (Encor 626) comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low-VOC multifunctional additive blends including TXMB:K-FLEX® 850S in ratios of (90:10) and (10:90). [Diagram 36] FIG. 1 shows the initial and final scrub resistance results (number of scrub cycles) achieved with another 100% acrylic binder (VSR-1050) comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low-VOC multifunctional additive blends including TXMB:K-FLEX® 850S in ratios of (90:10) and (40:60). [Figure 37] FIG. 1 shows the initial and final scrub resistance results (number of scrub cycles) achieved with a vinyl acrylic binder (Encor 379G) comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low-VOC multifunctional additive blends including TXMB:K-FLEX® 850S in ratios of (80:20) and (50:50). [Figure 38] FIG. 1 shows a side-by-side comparison of 1-day and 7-day block resistance results achieved with Encor 471 comparing TXMB, OE-400, K-FLEX® 975P, and two inventive low-VOC multifunctional additive blends containing TXMB:K-FLEX® 975P in ratios of (70:30) and (30:70). [Figure 39] FIG. 1 shows a side-by-side comparison of 1-day and 7-day block resistance results (ratings) achieved with EPS 2533 comparing TXMB, OE-400, K-FLEX® 975P, and two inventive low-VOC multifunctional additive blends containing TXMB:K-FLEX® 975P in ratios of (30:70) and (55:45). [Diagram 40]FIG. 1 shows a side-by-side comparison of 1-day and 7-day block resistance results achieved with Acronal 296D comparing TXMB, OE-400, K-FLEX® 975P, and two inventive low-VOC multifunctional additive blends containing TXMB:K-FLEX® 975P in ratios of (10:90) and (90:10). [Diagram 41] FIG. 1 shows a side-by-side comparison of 1-day and 7-day block resistance results achieved with Encor 626 comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low-VOC multifunctional additive blends containing TXMB:K-FLEX® 850S in ratios of (10:90) and (90:10). [Diagram 42] FIG. 1 shows a side-by-side comparison of 1-day and 7-day block resistance results achieved with VSR-1050 comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low-VOC multifunctional additive blends containing TXMB:K-FLEX® 850S in ratios of (10:90) and (40:60). [Diagram 43] FIG. 1 shows a side-by-side comparison of 1-day and 7-day block resistance results on Encor 379G comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low-VOC functional additive blends containing TXMB:K-FLEX® 850S in ratios of (50:50) and (80:20). [Diagram 44] FIG. 1 shows the gloss results (units) achieved with Encor 471 comparing TXMB, OE-400, K-FLEX® 975P, and two inventive low-VOC multifunctional additive blends containing TXMB:K-FLEX® 975P in ratios of (70:30) and (30:70). [Diagram 45]FIG. 1 shows gloss results achieved with EPS 2533 comparing TXMB, OE-400, K-FLEX® 975P, and two inventive low VOC multifunctional additive blends containing TXMB:K-FLEX® 975P in ratios of (55:45) and (30:70). [Diagram 46] FIG. 1 shows gloss results achieved with Acronal 296D comparing TXMB, OE-400, K-FLEX® 975P, and two inventive low-VOC multifunctional additive blends containing TXMB:K-FLEX® 975P in ratios of (90:10) and (10:90). [Figure 47] FIG. 1 shows gloss results achieved with Encor 626 comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low VOC multifunctional additive blends containing TXMB:K-FLEX® 850S in ratios of (10:90) and (90:10). [Figure 48] FIG. 1 shows gloss results achieved with VSR-1050 comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low-VOC multifunctional additive blends containing TXMB:K-FLEX® 850S in ratios of (90:10) and (40:60). [Figure 49] FIG. 1 shows gloss results achieved with Encor 379G comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low-VOC multifunctional additive blends containing TXMB:K-FLEX® 850S in ratios of (50:50) and (80:20). [Figure 50] FIG. 1 shows the dirt pickup resistance results (Δ%Y) achieved with Encor 471 comparing TXMB, OE-400, K-FLEX® 975P, and two inventive low-VOC multifunctional additive blends containing TXMB:K-FLEX® 975P in ratios of (70:30) and (30:70). [Figure 51]FIG. 1 shows the dirt pickup resistance results achieved with EPS 2533 comparing TXMB, OE-400, K-FLEX® 975P, and two inventive low VOC multifunctional additive blends containing TXMB:K-FLEX® 975P in ratios of (55:45) and (30:70). [Figure 52] FIG. 1 shows the dirt pickup resistance results achieved with Acronal 296D compared to TXMB, OE-400, K-FLEX® 975P, and one inventive low-VOC multifunctional additive blend containing TXMB:K-FLEX® 975P in a (90:10) ratio. [Figure 53] FIG. 1 shows the dirt pickup resistance results achieved with VSR-1050 comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low-VOC multifunctional additive blends containing TXMB:K-FLEX® 850S in ratios of (90:10) and (40:60). [Figure 54] FIG. 1 shows the dirt pickup resistance results achieved with Encor 626 comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low VOC multifunctional additive blends containing TXMB:K-FLEX® 850S in ratios of (10:90) and (90:10). [Figure 55] FIG. 1 shows the dirt pickup resistance results achieved with Encor 379G comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low-VOC multifunctional additive blends containing TXMB:K-FLEX® 850S in ratios of (50:50) and (80:20). [Figure 56] FIG. 1 shows the low temperature coalescence results (ratings) achieved with Encor 471 comparing TXMB, OE-400, K-FLEX® 975P, and two inventive low VOC multifunctional additive blends containing TXMB:K-FLEX® 975P in ratios of (70:30) and (30:70). [Figure 57]FIG. 1 shows low temperature coalescence results achieved with EPS 2533 comparing TXMB, OE-400, K-FLEX® 975P, and two inventive low VOC multifunctional additive blends containing TXMB:K-FLEX® 975P in ratios of (55:45) and (30:70). [Figure 58] FIG. 1 shows low temperature coalescence results achieved with Acronal 296D comparing TXMB, OE-400, K-FLEX® 975P, and two inventive low VOC multifunctional additive blends containing TXMB:K-FLEX® 975P in ratios of (90:10) and (10:90). [Figure 59] FIG. 1 shows low temperature coalescence results achieved with Encor 626 comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low VOC multifunctional additive blends containing TXMB:K-FLEX® 850S in ratios of (10:90) and (90:10). [Figure 60] FIG. 1 shows the low temperature coalescence results achieved with VSR-1050 comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low-VOC multifunctional additive blends containing TXMB:K-FLEX® 850S in ratios of (90:10) and (40:60). [Figure 61] FIG. 1 shows low temperature coalescence results achieved with Encor 379G comparing TXMB, OE-400, K-FLEX® 850S, and two inventive low VOC multifunctional additive blends containing TXMB:K-FLEX® 850S in ratios of (50:50) and (80:20). [Figure 62]1 is a photographic image showing wet adhesion results achieved in water-based direct-to-metal coatings applied to steel panels (Table 5) comparing the use of a blend of propylene glycol dibenzoate and dipropylene glycol n-butyl ether (left image) and the use of a low VOC multifunctional additive blend of the present invention including propylene glycol dibenzoate and benzyl alcohol (right image), where the multifunctional additive blend of the present invention provides a significant improvement in wet adhesion. [Figure 63] FIG. 1 shows the Koenig hardness results achieved over time for water-based direct-to-metal coatings (Table 5) containing blends of propylene glycol dibenzoate and dipropylene glycol n-butyl ether, and blends of butyl benzyl phthalate and dipropylene glycol n-butyl ether, and low VOC multifunctional additive blends of the present invention containing propylene glycol dibenzoate and benzyl alcohol. [Figure 64] FIG. 1 shows Koenig hardness results over time achieved for direct-to-metal coatings containing a 1:1 blend of PGDB:DPnB, a 1:1 blend of BBP:DPnB, and two inventive low-VOC multifunctional additive blends of PGDB:benzyl alcohol (1:1) and K-FLEX® 850S:benzyl alcohol (1:1). [Figure 65] FIG. 1 shows block resistance results (23° C.) achieved in direct-to-metal coatings containing a 1:1 blend of PGDB:DPnB, a 1:1 blend of BBP:DPnB, and two inventive low-VOC multifunctional additive blends of PGDB:benzyl alcohol (1:1) and K-FLEX® 850S:benzyl alcohol (1:1). [Figure 66]FIG. 1 shows block resistance results (50° C.) achieved in direct-to-metal coatings containing a 1:1 blend of PGDB:DPnB, a 1:1 blend of BBP:DPnB, and two inventive low-VOC multifunctional additive blends of PGDB:benzyl alcohol (1:1) and K-FLEX® 850S:benzyl alcohol (1:1). [Figure 67] FIG. 1 shows dry and wet adhesion results achieved for direct-to-metal coatings containing a 1:1 blend of PGDB:DPnB, a 1:1 blend of BBP:DPnB, and two inventive low-VOC multifunctional additive blends of PGDB:benzyl alcohol (1:1) and K-FLEX® 850S:benzyl alcohol (1:1). [Figure 68] FIG. 1 shows freeze-thaw results achieved with a styrene acrylic binder comparing TXMB, TEGDO, K-FLEX® 850S, and two inventive low VOC multifunctional additive blends containing benzyl alcohol and dibenzoate in various ratios (no data for TXMB as sample gelled). [Figure 69] FIG. 1 shows freeze-thaw results achieved with an all-acrylic binder comparing TXMB, TEGDO, K-FLEX® 850S, and two inventive low-VOC multifunctional additive blends containing benzyl alcohol and dibenzoate in various ratios. [Figure 70] 1 is a photographic image of Encor 626 blended with 2.5% by weight of the binder of the low VOC multifunctional additive blend of the present invention, X-3411, showing a stabilized polymer emulsion incorporating the low VOC multifunctional additive blend. [Figure 71] Photographic image of Encor 626 blended with 1.1% by weight benzyl alcohol relative to the binder showing aggregates / flocculants at the bottom of the jar, indicating that benzyl alcohol alone destabilizes the polymer (binder). [Figure 72]Photographic image of fully formulated Encore 471 Semi-Gloss with benzyl alcohol post-added at 3.95 wt% of the binder shows the formation of aggregates and flocculants, indicating that benzyl alcohol alone destabilizes the polymer (binder). [Figure 73] Photographic image of fully formulated semi-gloss Encor 471 using 7.9% by weight of X-3411 (equivalent to 3.95% by weight of benzyl alcohol) relative to the binder shows that a stable coating was obtained with a blend of benzyl alcohol and a dibenzoate according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0045] The present invention is directed to low VOC multifunctional additive blends for use in waterborne coatings and other waterborne polymeric film-forming compositions, which, in addition to coalescence, provide improved hardness and scrub resistance, hardness development, block resistance, dirt pickup resistance, wet adhesion, and corrosion resistance (flash rust resistance), among other properties, than can be achieved when conventional high-volatility or low-volatility coalescents are used alone. The present invention is also directed to methods for improving the performance of waterborne polymeric film-forming compositions by adding the coalescent compositions of the present invention, which are superior to those achieved when conventional high-volatility or low-volatility coalescents are used alone. The present invention is also directed to methods for preparing certain low VOC multifunctional additive compositions and / or waterborne polymeric systems by incorporating certain organic acids to improve the flash rust resistance of the waterborne film-forming compositions.
[0046] The terms are defined as follows: "Binder" is intended to mean and include the polymers and resins that make up the base of a paint or coating formulation or other aqueous polymeric film-forming composition. "Binder," "polymer," and "resin" are used interchangeably herein unless otherwise noted.
[0047] "High volatility," "high volatile," and "high VOC" are used interchangeably herein when used in connection with certain components of the multifunctional additive blend of the present invention. As will be understood, "VOC" means "volatile organic compound."
[0048] "Low volatility," "low volatile," and "low VOC" are used interchangeably herein when used in connection with certain components of the multifunctional additive blend of the present invention.
[0049] "Formulation" means and includes a paint or coating composition or other aqueous polymeric film-forming composition (defined below) that contains a binder (polymer), the low VOC multifunctional additive blend of the present invention, and other ingredients conventionally used in compositions.
[0050] "Aqueous polymeric film-forming composition" is intended to mean and include compositions that are known "film-formers", including, but not limited to, paints and other coatings (irrespective of the substrate being coated), membranes, film coatings, adhesives, glues, sealants, caulkings, and some inks. "Aqueous polymeric systems" and "aqueous polymeric film-formers" or "aqueous polymeric film-forming compositions" are used interchangeably herein. For the avoidance of doubt, an "aqueous coating" is also considered an "aqueous polymeric film-forming composition". Depending on the use or application, the terms "aqueous coating" or "paint" or "paint formulation" may be used in place of "aqueous polymeric film-forming composition".
[0051] "Multifunctional additive" or "multifunctional additive blend" or "low VOC multifunctional additive" or "low VOC multifunctional additive blend" are used interchangeably to describe the compositions of the present invention. "Multifunctional" is intended to mean and include the various functions provided by the low VOC multifunctional additive of the present invention, including, for example, improved hardness, rate of hardness development, scrub resistance, block resistance, dirt pickup resistance, wet adhesion, and corrosion (flash rust) resistance, among others, in addition to coalescence.
[0052] Specifically, the present invention is directed to low volatility (VOC) multifunctional additive blends that include a mixture of known low volatility (VOC) coalescing components and high volatility (VOC) components, some of which have not previously been known, recognized, or used as coalescents to date. The multifunctional additives of the present invention may optionally include certain organic acids, such as benzoic acid, for the purpose of improving flash rust resistance in waterborne polymer systems. Salts of organic acids may also be added to waterborne coatings containing the low VOC multifunctional additives of the present invention for the purpose of improving flash rust resistance.
[0053] The low VOC coalescent components for use in the multifunctional additive of the present invention include plasticizers. Suitable dibenzoate plasticizers include, but are not limited to, diethylene glycol dibenzoate (DEGDB), dipropylene glycol dibenzoate (DPGDB), 1,2-propylene glycol dibenzoate (PGDB), triethylene glycol dibenzoate, tripropylene glycol dibenzoate, such as a blend of dibenzoates of DEGDB and DPGDB, or a triple blend of DEGDB, DPGDB, and PGDB, and mixtures thereof. Suitable monobenzoate plasticizers include, but are not limited to, 2-ethylhexyl benzoate, 3-phenylpropyl benzoate, 2-methyl-3-phenylpropyl benzoate, isodecyl benzoate, isononyl benzoate, and mixtures thereof. Other benzoate esters and their blends are also suitable in the present invention. Suitable phthalate plasticizers include, but are not limited to, di-n-butyl phthalate (DBP), diisobutyl phthalate (DIBP), or butyl benzyl phthalate (BBP). Suitable terephthalate plasticizers include, but are not limited to, di-2-ethylhexyl terephthalate (DOTP), dibutyl terephthalate (DBT), or diisopentyl terephthalate (DPT). Suitable citrate plasticizers include, but are not limited to, acetyl tributyl citrate, tri-n-butyl citrate, and the like. Suitable 1,2-cyclohexanedicarboxylate ester plasticizers that can be used with selected polymer systems include diisononyl-1,2-cyclohexanedicarboxylate (Hexamoll® DINCH®, manufactured by BASF). Other lower VOC plasticizers will be known to those skilled in the art based on the disclosure herein.
[0054] Suitable non-plasticizing, low VOC coalescents for use in the low-VOC multifunctional additive of the present invention include, but are not limited to, triethylene glycol dioctanoate (TEGDO), Optifilm™ Enhancer 400 (OE-400) (triethylene glycol bis(ethylhexanoate-2), available from Eastman Chemical), and a mixture of purified diisobutyl esters of adipic, glutaric, and succinic acids (Coasol™ and Coasol™ 290 Plus, available from DOW). Other non-plasticizing, low VOC coalescents or film-formers will be known to those of skill in the art based on the disclosure herein.
[0055] The higher VOC components used in the low VOC multifunctional additive of the present invention include known high volatility coalescents as well as other high volatility components that are not known and have not been used as coalescing agents to date. Higher VOC components suitable for use in the blends of the present invention include, but are not limited to, glycol ethers used as coalescents, such as butyl cellosolve (ethylene glycol monobutyl ether), butyl Carbitol™ (diethylene glycol monobutyl ether), diethylene glycol monomethyl ether (DEGME), and dipropylene glycol n-butyl ether (DPnB), 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (TXMB), benzylamine, phenoxyethanol, phenylethanol, benzyl alcohol, benzyl benzoate, 3-phenylpropanol, 2-methyl-3-phenylpropanol, vanillin, β-methylcinnamyl alcohol (cypriol). Of these, TXMB has historically been a high VOC coalescent combined with OE-400 (a low VOC coalescent) in an effort to reduce costs and achieve lower VOC compounds. A comparative evaluation of this previously known combination against the coalescent of the present invention is shown in the Examples. It was not previously known, or even expected, that TXMB would have a synergistic effect when blended with dibenzoates. Surprisingly, the results show that the TXMB:dibenzoate blend works much better than the previously known TXMB:OE-400 blend.
[0056] Higher VOC ingredients previously unknown, unrecognized, or unusable as coalescents, such as benzylamine, phenoxyethanol, phenylethanol, benzyl alcohol, benzyl benzoate, 3-phenylpropanol, 2-methyl-3-phenylpropanol, vanillin, or β-methylcinnamyl alcohol (cypriol), have unexpected results when blended with the lower VOC coalescents listed above. When used alone, some of these ingredients were evaluated as being incompatible with typical coating polymers and were actually thought to destabilize them. However, when combined with lower VOC coalescent ingredients as disclosed herein, surprisingly, the polymers were not destabilized. Blending these higher VOC ingredients with low VOC coalescents unexpectedly results in improved performance while still providing low VOC content for coatings and other waterborne polymer systems. Here, for example, a blend of benzyl alcohol:850S improved the incorporation of benzyl alcohol into the polymer emulsion, resulting in a more stable product, a result that was totally unexpected since benzyl alcohol was known to be incompatible with acrylic and styrene-acrylic binders, even at low loading levels.
[0057] Other, higher VOC content ingredients will be known to those of skill in the art based on the disclosure herein.
[0058] Other components that may be included in the low-VOC multifunctional additive of the present invention include corrosion inhibitors, particularly flash rust inhibitors. Flash rust resistance is particularly important in direct water-based coatings on metals, among other applications. Organic acids, such as benzoic acid, phthalic acid, and succinic acid, improve the flash rust resistance of certain coatings. However, organic acids, such as benzoic acid, are known to have very low solubility in water, which poses challenges when incorporating them into water-based polymeric film-forming compositions.
[0059] The low VOC multifunctional additive blend of the present invention provides a novel method for incorporating an organic acid, such as benzoic acid, into an aqueous polymeric film-forming composition. In one method, benzoic acid is first incorporated into a low volatility dibenzoate component by using a 1% to 30% molar excess of benzoic acid in the reaction to synthesize the dibenzoate. The resulting low volatility dibenzoate ester, containing an excess of acid, is then combined with a high volatility component to form the low VOC multifunctional additive blend of the present invention.
[0060] Alternatively, the benzoic acid can be mixed all at once with the low volatility and high volatility components to form the low VOC multifunctional additive blend of the present invention, or the benzoic acid can be added to a preformed low VOC multifunctional additive blend of the present invention which is then added to a water-based coating to improve the wet adhesion, initial rate of hardness development, and flash rust resistance of the coating.
[0061] In yet another method, benzoic acid is first dissolved in a pre-synthesized dibenzoate in a concentration sufficient to improve flash rust resistance when added to a direct-to-metal water-based coating formulation, and then a highly volatile component is added to form a low VOC multifunctional additive blend.
[0062] Preferred embodiments for improving flash rust resistance include benzoic acid, dibenzoates, and benzyl alcohol, although other organic acids may be incorporated into the high and low volatility components of the multifunctional additive of the present invention in the manner described herein.
[0063] Although salts of organic acids, such as sodium benzoate, are generally insoluble for the purposes of the above-mentioned method, they are soluble in water and can be subsequently added to the water-based coating containing the low VOC multifunctional additive of the present invention to improve flash rust resistance, wet adhesion and initial rate of hardness development. As an example, sodium benzoate may be added to a water-based coating containing benzyl alcohol as the high volatility component and propylene glycol dibenzoate as the low volatility component.
[0064] Thus, the blend of the low-VOC multifunctional additive of the present invention includes at least one high volatility component and at least one low volatility component. At least one component of the blend preferably has a molecular structure containing an aromatic ring, but the present invention is not limited thereto. Depending on the application / use, an organic acid may be incorporated or added to the low-VOC multifunctional additive blend of the present invention as described above. Alternatively, a salt of an organic acid may be added to the aqueous polymeric film-forming composition containing the low-VOC multifunctional additive blend of the present invention.
[0065] The low-VOC multifunctional additive blend of the present invention can be used in a wide variety of water-based coatings or other water-based polymeric film-forming compositions. The present invention is not limited to any particular polymer. In general, any known polymer that can be formulated into a paint or coating can be used in combination with the novel low-VOC multifunctional additive blend according to the present invention to prepare a paint or coating with low VOC content without sacrificing performance performance. In addition, the low-VOC multifunctional additive blend can be used with polymeric compositions that rely in part or in whole on the formation of a film, including, but not limited to, adhesives, glues, sealants, caulkings, and some ink compositions.
[0066] The aqueous polymeric film-forming composition may include various polymers. Suitable polymers include, but are not limited to, various latexes and vinyl polymers such as vinyl acetate, vinylidene chloride, diethyl fumarate, diethyl maleate, or polyvinyl butyral; various polyurethanes and their copolymers; polyamides, various polysulfides; nitrocellulose and other cellulosic polymers; polyvinyl acetate and their copolymers, ethylene vinyl acetate, and vinyl acetate-ethylene; and various polyacrylates and their copolymers.
[0067] Acrylates in particular constitute a large group of polymers of various hardnesses that may be used with the multifunctional additive blends of the present invention, including, but not limited to, various polyalkyl methacrylates, such as methyl methacrylate, ethyl methacrylate, butyl methacrylate, cyclohexyl methacrylate, or allyl methacrylate; various aromatic methacrylates, such as benzyl methacrylate; various alkyl acrylates, such as methyl acrylate, ethyl acrylate, butyl acrylate, or 2-ethylhexyl acrylate.
[0068] Acrylics are also useful polymers and include, but are not limited to, 100% acrylic, acrylic copolymers, acrylics such as methacrylic acid; vinyl acrylics; styrenated acrylics, and acrylic-epoxy hybrids.
[0069] Other polymers include, but are not limited to: alkyds, epoxies, phenol-formaldehyde types; melamines; vinyl esters of versatic acid, etc. Some polymers, such as alkyds, typically do not require a coalescent, but may benefit from the low VOC multifunctional additive blends of the present invention in terms of early hardness development, or initial rate of hardness development. They may also benefit from other performance improvements as described herein. Other polymers useful in waterborne coatings or other waterborne polymeric film-forming compositions will be known to those of skill in the art based on the disclosure herein.
[0070] The ratio of high volatility (VOC) components to low volatility (VOC) components in the multifunctional additive blends of the present invention can vary from about 10: 1 to about 1: 10. The ratio can be varied to suit the particular components of the multifunctional additive blend, the coating formulation, and / or the intended application or use.
[0071] Generally, the amount of the multifunctional additive blend of the present invention used in a coating formulation will depend on the amount needed to achieve a MFFT (minimum film forming temperature) of 32°F to 40°F (approximately 0° to 4.4°C), which is the temperature standard used to determine whether a paint or coating can be applied in cold weather. The amount of the low VOC multifunctional additive blend of the present invention is expressed as a percentage of the binder (wt% of binder (polymer)) based on 100 grams of binder (polymer or resin) in the coating formulation, or as a percentage of the formulation based on the total weight of all ingredients in the formulation (wt%). In coatings, as the volume concentration of pigment increases, the percentage of the multifunctional additive blend of the present invention in the formulation decreases while the percentage of binder remains constant.
[0072] Examples of amounts of the multifunctional additive blend of the present invention based on percentage of binder (polymer) or percentage in the formulation are described in the Examples. The preferred percentage of binder amount ranges from about 0.1% to about 15% based on 100 grams of binder, but the amount will vary depending on the particular binder and other ingredients used. The preferred percentage in the formulation (based on the total weight of all ingredients) ranges from about 0.8% to about 5% by weight based on the total weight of the ingredients in the formulation.
[0073] Applications for using the low VOC multifunctional additive blend of the present invention include, but are not limited to, architectural coatings, industrial coatings, OEM coatings, interior and exterior paints, metal coatings (including direct to metal coatings), marine coatings, film coatings, vinyl film compositions, plastic coatings, wood coatings and treatments, paper coatings, fabric coatings, textile coatings, wallpaper coatings, decorative coatings, structural coatings, cement coatings, concrete coatings, floor coatings, varnishes, and inks. Other useful applications include use in adhesive compositions, glues, or other coalescents or water-based polymeric film-forming compositions requiring film formation, such as sealants and caulkings. Still other useful applications will be known to those skilled in the art.
[0074] The low VOC multifunctional additive of the present invention also finds application as a vehicle or carrier for pigments or colorants (colorants, dyes) added to already prepared aqueous polymer systems. The amount of the low VOC multifunctional additive blend used in this application will vary depending on the particular aqueous polymer system, the identity and type of pigment or colorant, and the amount of color required in the aqueous polymer system.
[0075] Certain components of the low-VOC multifunctional additive blends have been shown to improve formulation robustness in relation to in-can storage, potentially providing the added benefit of significantly reducing the in-can antimicrobial content previously required, depending on the formulation and process.
[0076] The present invention is further illustrated by the following non-limiting examples. EXAMPLES
[0077] Working Example Test substances <Highly volatile components>: 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (TXMB or TMPDMIB) (commercially available as Texanol™ from Eastman) Benzyl alcohol 3-Phenylpropanol (3PP) 2-Methyl-3-phenylpropanol (2M3PP) Vanillin β-Methylcinnamyl alcohol (Cypriol)
[0078] <Low VOC plasticizers / coalescents / film formers>: K-FLEX® PG (Propylene Glycol Dibenzoate (PGDB)) K-FLEX® 500 (DEGDB / DPGDB blend) K-FLEX® 850S or 850S (a new grade DEGDB / DPGDB blend) K-FLEX® 975P, or 975P (a novel dibenzoate triblend containing DEGDB / DPGDB / 1,2-PGDB) Triethylene glycol dioctanoate (TEGDO), multiple sources Optifilm™ Enhancer 400, or OE-400 (according to its Safety Data Sheet, triethylene glycol bis(ethylhexanoate-2), available from Eastman Chemical)
[0079] <Examples of low VOC multifunctional additive blends of the present invention>: X-3411, 1:1, benzyl alcohol:K-FLEX® 850S X-3412, 1:2, benzyl alcohol:K-FLEX® 850S X-3413, 1:3, benzyl alcohol:K-FLEX® 850S TXMB:K-FLEX® Dibenzoate (TXMB:K-FLEX® 850S or 975P in various ratios between 10:1 and 1:10) Benzyl alcohol: OE-400, 1:1 (unless otherwise specified) Cypriol:K-FLEX® 850S, 1:1 3-PP:K-FLEX® 850S, 1:1 2M3PP:K-FLEX®850S, 1:1 Note: The above ratios are for the materials tested in the examples, and the range of ratios of high VOC components to low VOC components in the multifunctional additive blends of the present invention can vary from 10:1 to 1:10 and still be within the scope of the present invention.
[0080] Comparative Coalescent Blends Reported: TXMB:OE-400 (1:1 ratio in all examples) <Coating>: Traditional binders for coating materials were selected to evaluate the ability of the multifunctional additive blend of the present invention to provide coalescence and improved properties. Experimental coatings were used with various binders and with various glass transition temperatures and minimum film formation temperatures. The present invention is not limited to those used in the coatings evaluated. The following binders (polymers, resins) were evaluated: Styrene-acrylic resin (available from Arkema as Encor® 471, T g approx. 44℃) Styrene-acrylic resin (available as EPS® 2533 from EPS Materials, T g :N / A) 100% acrylic resin (available from Arkema as Encor® 626, T g approx. 29℃) 100% acrylic resin (available from Dow Chemical as Rhoplex™ VSR 1050, T g approx. 17℃) Styrene-acrylic resin (available as Acronal® 296D from BASF, T g approx. 22℃) Styrene-acrylic resin (available from Arkema as Encor® 379G, T g approx. 19℃) 100% acrylic resin (available from Specialty Polymers Inc. as RayCryl 1207 (a special grade offered without in-can antimicrobial agents) g approx. 19℃)
[0081] [Test method]: pH: ASTM E70 The pH of the coating was measured using a Beckman 310 pH meter equipped with a universal electrode. The pH of the coating was adjusted to a pH range of 8.5-9.5 using ammonium hydroxide (28%).
[0082] Stormer viscosity: ASTM D562 The initial Stormer viscosity was measured using a Brookfield KU-2 viscometer equipped with a paddle type. Rheology modifiers were added to adjust the initial viscosity to within the range of 90-110 KU.
[0083] MFFT:ASTM D2354 The minimum film formation temperature was evaluated using a Gardco MFFT Bar 90 instrument. Polymer latex emulsions blended with nonionic surfactants and coalescents were drawn down using a MFFT drawdown applicator and film formation was evaluated after 1 hour. The temperature gradient set on the instrument was -5°C to 13°C. The film formation temperature was evaluated by visual inspection and the temperature was measured using a separate temperature probe.
[0084] Low Temperature Coalescence (LTC): ASTM D7306 The paint and equipment were conditioned for 4 hours at 40° F. Paint was drawn down onto Leneta Form HK to 10 mils wet. The film was allowed to dry horizontally at 40° F. for 18 hours and rated (laboratory grade, 10=excellent, 0=very poor).
[0085] Scrubbing performance: ASTM D2486 Coatings were applied to Leneta F121-10N charts using a 7 mil Dow applicator bar and allowed to dry for 7 days at 23°C and 50% RH. Scrubbing was measured using a Gardco D10 Washability and Weartester. A 10 mil shim with abrasive media (SC-2) was employed. Initial damage was recorded and complete damage was defined as a continuous thin line across the shim.
[0086] Block Resistance: ASTM D4946 The coatings were applied to Leneta type WB charts using a 3 mil bird film applicator and allowed to dry for 7 days at 23°C and 50% relative humidity in an environmentally controlled room. Samples measuring 1.5 inches square were prepared and oriented with a 1 kg weight placed on a No. 8 stopper at ambient temperature or 120°F for 30 minutes, coating surface to coating surface. The samples were then allowed to equilibrate for 30 minutes at room temperature and then evaluated by "blind" testing to avoid prejudice.
[0087] Gloss:ASTM D523 Coatings were applied to Leneta type WB charts using a 3 mil Bird film applicator and allowed to dry for 7 days in an environmentally controlled room at 23°C and 50% relative humidity. Gloss measurements were performed in triplicate using a Gardco micro-Tri-gloss meter model 4446.
[0088] Thermal stability: ASTM D1849 Tested for 2 weeks at 120° F. Initial and final viscosities were measured.
[0089] Flow and leveling: ASTM D4062 The paint was applied using a Leneta test blade and then the dried paint was graded.
[0090] Hardness / Hardness Development: ASTM D4366A Coatings were applied to aluminum A36Q panels using a 3 mil Bird film applicator and dried in an environmentally controlled chamber at 23°C and 50% relative humidity. Hardness was measured using a Gardco Koenig and / or Persoz Hardness Rocker with the corresponding pendulum for each test. Hardness values were reported as the average of three measurements.
[0091] Freeze / thaw stability: ASTM D2243 Freeze at 0° C. and thaw at ambient temperature. Three cycles were used. Washability: Paint samples were drawn down onto a Leneta P-121-10N scrub chart using a 7 mil Dow blade. The panels were then allowed to air dry in a horizontal position for 7 days. For each panel, the soil was applied in a 1 inch wide area with 0.25 inch spacing between soils. The stain materials tested were: lipstick (Rimmel, Rosseto #510, red), crayon (Crayola, red), ketchup (Hunts Tomato Ketchup, no preservatives), mustard (French's Classic Yellow prepared mustard packet), pencil (Papermate Micrado Classic, HB#2), coffee (Safeway Signature Select: sun Kissed Blonde), food coloring (McCormick Food Color & Egg Dye, green), wine (Gnarly Head Wines, old vine zinfandel, 2016, Lodi zinfandel), permanent marker (Sharpie Magnum, black), ballpoint pen (Papermate Flexgrip Ultra 0.8F, black), and water-based marker (Mr. Sketch, blue). The coffee, wine, and food coloring were applied using a Kim wipe by placing a dry Kim wipe over the panel and saturating it with the stain material. The soiled material was left for 1 hour, after which any excess was removed. Each panel was cleaned for 50 cycles using a C-31 sponge with 10 g of Formula 409 multipurpose-lemon hard surface cleaner. Permanent marker, water-based marker, and ballpoint pen soiled materials were cleaned separately to avoid bleeding. The panels were then rinsed with water, blotted dry, and left to dry completely in a horizontal position overnight. A colorimeter was used to measure the Δ(Delta)E of the stained area versus the white uncleaned area. Visual evaluation was also performed.
[0092] Dust absorption: Paint samples were applied by 3 mil drawdown onto aluminum Q36 panels. The panels were allowed to air dry in a horizontal position for 7 days. The top half of the panel was covered and synthetic dust was sprinkled evenly over the uncoated area. The panel was placed in a 50°C oven for 30 minutes. The panel was removed from the oven and tapped to remove any loose dust. The top of the panel was uncovered. The %Y reflectance of the test and non-test areas was read.
[0093] Scrub Resistance: ASTM D6736
[0094] Freezing and thawing: ASTM D2243 Prior to commencing the freeze-thaw cycles, the formulated coatings were allowed to equilibrate for 7 days at 23° C. and 50% relative humidity in an environmentally controlled room. Samples were subjected to three freeze cycles. Each freeze-thaw cycle consisted of placing the sample in a −18° C. freezer for 17 hours, then allowing it to equilibrate at room temperature for 7 hours, then measuring the viscosity, then immediately repeating the freeze-thaw cycle. Viscosity was measured using a Stormer viscometer equipped with a paddle-type rotor.
[0095] Flash Rust: Prior to drawdown, the formulated coatings were allowed to equilibrate for 7 days at 23°C and 50% relative humidity in an environmentally controlled room. The sealed polycarbonate boxes were placed in an oven set at 50°C along with a tray filled with water and allowed to equilibrate overnight. 0.025g of synthetic soil was rubbed onto cold rolled steel panels for 30 seconds. Excess soil was removed from the surface using compressed air. A 3 mil Bird film applicator was used to draw down the coating onto each panel, which was then immediately sprayed with a mist of water. The panels were then immediately placed into the equilibrated polycarbonate chamber in the oven. After 90 minutes, the test panels were removed and rated for rust formation on a scale of 0 to 4. A scale of 0 would correspond to no rust formation and a scale of 4 would correspond to severe flash rust. Each test was performed in duplicate and displayed alongside a negative control panel.
[0096] Wet adhesion: ASTM D3359 Method B: Coatings were drawn down at 6 mils (wet) onto cleaned cold rolled steel panels and dried for 21 days under standard ASTM conditions. The panels were completely immersed in deionized water for 60 minutes. The panels were gently tapped dry for 1 minute. Three specimens were cross-cut on the same panel using a 5-tooth 5mm blade (PA-2253). Intertape 51596 was cut to a 3 inch length and the untouched center was placed over the cross-cut. The tape was rubbed vigorously once with an index finger. After 60 seconds, the tape was quickly pulled away and graded using the ASTM method.
[0097] Other test methods used are given in the following table:
[0098] [Table 1]
[0099] Paints used in the examples Coatings are generally combinations of pigments, binders, solvents, and other additives such as coalescents or coalescence aids. The binder (i.e., resin or polymer) is usually the coating's name, such as acrylics, polyurethanes, styrene-acrylics, etc. The binder is responsible for the adhesion, durability, flexibility, gloss, and other physical properties of the coating composition. Exemplary coating compositions used in the examples are shown in Tables 1, 2, 3, and 4 below, but the invention is not limited thereto. The flat coating contained 45% PVC, the semi-gloss contained 14% PVC, and all coatings were 40% solids as a base, not taking into account the addition of coalescents.
[0100] [Table 2]
[0101] [Table 3]
[0102] [Table 4]
[0103] [Table 5]
[0104] [Table 6]
[0105] It has been discovered that by formulating coatings using low VOC multi-functional additive blends including highly volatile compounds such as TXMB, benzylamine, phenoxyethanol, phenylethanol, benzyl alcohol, benzyl benzoate, 3-phenylpropanol (3-PP), 2-methyl-3-phenylpropanol, vanillin, or β-methylcinnamyl alcohol (cypriol) in combination with traditional low VOC coalescents or film-formers such as, but not limited to, dibenzoate esters, monobenzoates, phthalates, terephthalates, 1,2-cyclohexanedicarboxylate esters, citrates, OE-400, TEGDO, and the like, unexpected improvements in performance are achieved compared to traditional high VOC coating formulations including the industry standard high VOC coalescent 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (TXMB) alone or in combination with OE-400 / TEGDO while maintaining lower VOC content. The low VOC multifunctional additive blends of the present invention also exhibited unexpected improvements in performance with minimal increase in VOC content compared to the use of conventional low VOC coalescent compounds alone. The improvements may vary depending on the use or application of the specific components of the formulation.
[0106] Typically, the loading level of the coalescent agent is determined by determining the amount required for each binder to achieve a minimum film formation temperature (MFFT) of less than 40°F (about 4.4°C). In the examples herein, the loading levels for the low-VOC multi-function additives are expressed as a percentage (%) of additive to binder based on 100 grams of binder unless otherwise noted. The low-VOC multi-function additive levels can sometimes be expressed as a weight percent based on the total weight of the formulation. The VOC content in each formulation assumes 100% TXMB, according to EPA Method 24. The VOC content for K-FLEX® 850S has been previously published (2.2 weight percent, according to ASTM D2369), and was used to evaluate the VOC.
[0107] Example 1: Evaluation of scrub resistance In addition to coalescence, the dibenzoate coalescent agent provides benefits in terms of scrub resistance performance in the coating compared to that achieved with TXMB alone, however results may vary depending on the particular dibenzoate used and the nature of the binder or formulation.
[0108] Figures 1-6 show the improved scrub resistance performance of the low VOC multifunctional additive of the present invention using blends of TXMB (high volatility component) and low volatility component (dibenzoate ester) in various ratios versus paints made with each of these components alone. In the experimental samples, the high volatility component TXMB is combined with the lower VOC dibenzoate to form the lower VOC multifunctional additive. Figure 1 shows the scrub resistance results achieved with a harder styrene-acrylic resin (Encor 471) using TXMB alone, K-FLEX® 975P alone, and a 70:30 blend of TXMB to 975P. The blended low VOC multifunctional additive had lower VOC than the traditional high volatility component TXMB (still higher than the commercial dibenzoate) and synergistically improved scrub resistance compared to the TXMB control and the commercial dibenzoate alone.
[0109] Figure 2 shows similar scrub resistance results achieved with another styrene-acrylic resin (EPS 2533) comparing TXMB alone, K-FLEX® 975P alone, and a 70:30 blend of TXMB to 975P. Figure 3 shows similar scrub resistance results achieved with another styrene-acrylic resin (Acronal 296D) with a low VOC multifunctional additive blend of 10:90 TXMB:975P, but with much lower VOCs compared to the other styrene-acrylic resins.
[0110] Similar scrub resistance results were obtained when using a blended low VOC multi-functional additive containing TXMB and K-FLEX® 850S. Figure 4 also shows similar scrub resistance results achieved with a multi-functional additive containing TXMB:K-FLEX® 850S at 10:90 when used with a 100% acrylic resin (Encor 626) and having low VOC. Figure 5 also shows similar results achieved with the same multi-functional additive (TXMB:850S at 10:90) when used with yet another 100% acrylic resin (VSR 1050). FIG. 6 also shows similar results achieved with a vinyl acrylic resin (Encor 379G) using a multifunctional additive with 80:20 (TXMB:850S). This multifunctional additive blend also had low VOCs. Further scrub resistance data for various multifunctional additive blends of (TXMB:850S) and (TXMB:975P) are described in Example 21.
[0111] Further scrub resistance was determined using ASTM D2486 for Encor 471 and Encor 626 flat and semi-gloss samples, comparing uncored samples, TXMB, OE-400, K-FLEX® 850S, three inventive low VOC multi-functional additive blends based on dibenzoates X-3411, X-3412, and X-3413, TXMB:OE-400 (1:1 ratio), and another inventive low VOC multi-functional additive blend, benzyl alcohol:OE-400 (1:1 ratio). The results are shown in Figures 21(a) (initial) and 21(b) (final). The inventive multi-functional additive X-3413 showed improved scrub resistance compared to TXMB and comparable scrub resistance to OE-400 and K-FLEX® 850S on the Encor 626 semi-gloss samples. In the flat samples and Encor 471 semi-gloss, X-3411, X-3412, and X-3413 performed comparable to other coalescents and blends.
[0112] The results thus obtained showed a significant improvement in scrub resistance with the blended multi-functional additive of the present invention compared to that achieved with the conventional high volatility TXMB coalescent and the lower VOC dibenzoate coalescent alone. Although the lower VOC dibenzoate coalescent had the lowest VOC, the blended multi-functional additive containing dibenzoate and TXMB still had a significantly lower VOC compared to the conventional high VOC coalescent TXMB alone.
[0113] Example 2: Koenig hardness Hardness testing using the ASTM D4366A method was performed on the following: Encor 471 flat and semi-gloss samples, Encor 626 flat and semi-gloss samples, TXMB, OE-400, K-FLEX® 850S, and three of the multifunctional additive blends of the present invention (X-3411, (1:1) benzyl alcohol:K-FLEX® 850S; X-3412, (1:2) benzyl alcohol:K-FLEX® 850S; X-3413, (1:3) benzyl alcohol:K-FLEX® 850S). The results for the flat samples (Encor 626 and Encor 471) are shown in Figures 9(a) and 9(b), both of which also show a comparison to the uncored samples.
[0114] Hardness results for Encor 471 and Encor 626 are shown in Figures 9(c), 9(d), and 9(e) comparing TXMB, OE-400, K-FLEX 850S, three inventive multi-functional additive blends X-3411, X-3412, and X-3413, a blend of TXMB:OE-400 (1:1 ratio), and two additional inventive multi-functional additive blends benzyl alcohol:OE-400 (1:1 ratio), β-methylcinnamyl alcohol (CYP or cypriol):850S (1:1 ratio), and an uncoalesced sample. Figure 9(e) shows the hardness development when K-FLEX® 850S is combined with the volatile components β-methylcinnamyl alcohol or Cypriol (CYP), 3-phenylpropanol (3PP), and 2-methyl-3-phenylpropanol (2M3PP), all in a 1:1 ratio. Each of these blends shows improved hardness development over that of the higher VOC TXMB control shown in Figure 9(c).
[0115] Blends of TXMB and OE-400 are known and reportedly practiced in the industry to reduce cost and volatility, yet the unexpected hardness achieved using the multifunctional additive blends of the present invention compared to the multifunctional additive blends of the present invention was not exhibited by the industry practiced TXMB:OE-400 blends.
[0116] The results showed that the multifunctional additive blend of the present invention performed significantly better while still achieving coalescence. Hardness was much improved over that achieved using the low VOC coalescents OE-400 and K-FLEX® 850S alone, or the industry practice of blending TXMB:OE-400. The results with the multifunctional additive blend of the present invention were significantly improved when compared to the industry standard high volatility coalescent, TXMB, but not to the same extent as OE-400 and K-FLEX® 850S. Surprisingly, a blend of a high volatility component (TXMB) and a low volatility component (OE-400) has been used in the past, but the performance of this particular blend was significantly lower than that of the multifunctional additive blend of the present invention.
[0117] Example 3: Grading of Blockiness Block resistance testing at ambient temperature and 50° C. using ASTM D4946 was performed on Encor 471 flat and semi-gloss samples and Encor 626 flat and semi-gloss samples containing TXMB, K-FLEX® 850S, and three of the inventive multifunctional additive blends (X-3411, 1:1 benzyl alcohol:K-FLEX® 850S; X-3412, 1:2 benzyl alcohol:K-FLEX® 850S; X-3413, 1:3 benzyl alcohol:K-FLEX® 850S), TXMB:OE-400 (1:1 ratio), and the inventive multifunctional additive blend benzyl alcohol:OE-400 (1:1 ratio). Historically, high VOC coalescents have performed extremely well in block resistance testing.
[0118] The results are shown in Figures 10 and 11. All of the coalescents and multifunctional additive blends performed equally well on the flat samples at ambient or 50°C. On the semi-gloss samples at ambient temperatures, the multifunctional additive blends of the present invention performed equally well to TXMB alone, and equally or better than OE-400 and K-FLEX® 850S alone. At 50°C, the multifunctional additive blends of the present invention performed better on the Encor 471 samples than TXMB, OE-400, K-FLEX® 850S, and the industry practice of TXMB:OE-400 blends. X-3411 and the benzyl alcohol:OE-400 blend performed better than TXMB, OE-400, K-FLEX® 850S, and the industry practiced TXMB:OE-400 blend, while X-3412 and X-3413 performed comparable to the other coalescents and blends.
[0119] Example 4: MFFT Testing and Calculated VOC Addition to Formulations The amounts of TXMB, K-FLEX® 850S, and three ratios of benzyl alcohol to K-FLEX® 850S (multi-functional additives of the present invention, X-3411, X-3412, and X-3413) were evaluated to determine the effectiveness of two binders, namely, Encor 626 acrylic resin (T g , about 29°C) and Encor 471 styrene-acrylic resin (T gThe amount of coalescent required to achieve a MFFT (minimum film formation temperature) of 4.4°C at 100°C (approximately 44°C) was determined. The amount of VOC (g / L) contributed to the wet paint (including water) and dry paint (removing water) was calculated. Results with Encor 626 acrylic resin indicate that the amount of the multi-function additive of the present invention required to achieve a MFFT of 4.4°C was less than that required for the dibenzoate K-FLEX® 850S alone, and was similar or slightly less than that required for TXMB alone, depending on the ratio of benzyl alcohol to K-FLEX® 850S. The calculated VOC contribution was higher for all of the benzyl alcohol / K-FLEX® 850S combinations of the present invention compared to K-FLEX® 850S alone, but was significantly lower than that calculated for the highly volatile TXMB alone. The Encor 471 results show that the amount of the multifunctional additive of the present invention required to achieve a MFFT of 4.4° C. is less than that required for the dibenzoate K-FLEX® 850S alone, and is similar or slightly less than that required for TXMB alone, depending on the ratio of benzyl alcohol to K-FLEX® 850S. The amounts required and VOC calculations are shown in the table below.
[0120] [Table 7]
[0121] [Table 8]
[0122] Example 5: Fluidity and leveling properties Using the ASTM D4062 method, the flow and leveling properties were evaluated for Encor 471 (flat), Encor 471 (semi-gloss), Encor 626 (flat), and Encor 626 (semi-gloss) samples and compared to TXMB, OE-400, K-FLEX® 850S, X-3411 (1:1 benzyl alcohol:K-FLEX® 850S), X-3412 (1:2 benzyl alcohol:K-FLEX® 850S), and X-3413 (1:3 benzyl alcohol:K-FLEX® 850S). Flow and leveling properties are highly sensitive to viscosity, with higher viscosity resulting in poorer flow. Despite similar viscosities (Stormer), the inventive multifunctional additive blend X-3413 achieved higher flow and leveling ratings in both Encor 471 samples (flat and semi-gloss) than any other coalescent or blend tested. In the Encor 471 semi-gloss samples, X-3411 and X-3412 performed as well as OE-400 and K-FLEX® 850S, and better than TXMB. In the Encor 626 semi-gloss samples, all of the inventive multifunctional additive blends (X-3411, X-3412, and X-3413) performed at least as well as the other coalescents tested. The results achieved are shown in Figure 7(a) and a comparison of the uncoalesced sample and the TXMB:OE-400 (1:1 ratio) and benzyl alcohol:OE-400 (1:1 ratio) blends is shown in Figure 7(b).
[0123] Example 6: Scrub Resistance The Encor 471 flat and Encor 626 flat samples were evaluated for scrub resistance on uncored samples and samples containing TXMB, OE-400, K-FLEX® 850S, X-3411, X-3412, and X-3413. Scrub resistance was tested on the flat formulations only. The lower the percentage increase in gloss (%) after 20 brush strokes with cheesecloth, the better the rating. The X-3413 multifunctional additive blend of the present invention had the lowest value of all the coalescents or blends evaluated on the Encor 626 samples, while the X3411 and X3412 multifunctional additive blends performed slightly better or equivalent to the other conventional coalescents. The results achieved are compared to the uncored samples as shown in FIG. 8.
[0124] Example 7: Low-temperature coalescence Low temperature coalescence was evaluated on Encor 471 flat formulation (10 mil). The coalescents and blends evaluated were: TXMB, OE-400, K-FLEX® 850S, X-3411 (1:1 benzyl alcohol:K-FLEX® 850S), X-3412 (1:2 benzyl alcohol:K-FLEX® 850S), and X-3413 (1:3 benzyl alcohol:K-FLEX® 850S). The results achieved are shown in the photograph (Figure 12(a)). The results show that the multifunctional additive blend of the present invention performed better in low temperature coalescence than the other coalescents among all the binders with each individual coalescent or blend optimized to achieve a MFFT of 4.4°C.
[0125] Additional low temperature coalescence at 10 mil thickness using the ASTM D7306 method was performed on flat and semi-gloss samples of Encor 471 and Encor 626 comparing uncored samples, TXMB, OE-400, K-FLEX 850S, X-3411, X-3412, X-3413, a blend of TXMB:OE-400 (1:1 ratio) and a blend of benzyl alcohol:OE-400 (1:1). The results are shown in Figure 12(b).
[0126] Example 8: Antibacterial effect The antimicrobial efficacy of the more volatile component, 3-phenylpropanol, at low concentrations was evaluated using the USP 51 (United States Pharmacopeia) test method. Soy broth was inoculated at pH 8.0 with the following bacterial strains: A. brasiliensis (filamentous fungus), P. aeruginosa (gram-negative), E. coli (gram-negative), S. aureus (gram-positive), and C. albicans (yeast). Figures 13(a), 13(b), 13(c), 13(d), and 13(e) are contour plots showing the log reduction over time for 3-phenylpropanol concentrations ranging from 0.25% to 2.5% by weight. Particularly good efficacy was observed against gram-negative bacteria and yeast, but log reductions over time were achieved at higher concentrations for all organisms tested.
[0127] The ASTM D2574 test method was used to determine the antimicrobial performance of the multifunctional additive blend of the present invention against P. aeruginosa and K. aerogenes. The coatings were challenged with 10 7The bacteria were inoculated at an in-can concentration of 1000 cfu / g. Inoculation continued every 7 days until the coating failed to completely kill the bacteria by the 7th day. Each 7-day period is referred to as a "round." As can be seen from the results below, the benzyl alcohol / dibenzoate (K-FLEX® 850S) multifunctional additive blend (X-3411) far surpassed the antimicrobial efficacy achieved by the negative control, the latter of which was ineffective against K. aerogenes after 3 rounds.
[0128] [Table 9]
[0129] [Table 10]
[0130] Loading of 1% by weight of the total formulation with coalescent agent satisfactorily passed all eight inoculations of the challenge test with no recovery of bacteria at the seventh day mark.
[0131] The antimicrobial effect of the multifunctional additive blend of the present invention offers formulators potential benefits in applications requiring microbial resistant coatings and allows for reduced concentrations of traditional antimicrobial additives required in formulations.
[0132] The above results demonstrate that the multi-functional additive blends of the present invention are truly multi-functional in that they not only provide improved film formation (coalescence) at lower or equivalent loading levels when compared to conventional high VOC and low VOC coalescents alone, provide lower VOC content when compared to conventional high VOC coalescents used alone, provide improved hardness and scrub resistance when compared to conventional high and low VOC coalescents alone, and provide equivalent or better block resistance and flow and leveling when compared to conventional coalescents, but also have potential antimicrobial effectiveness when tested according to standard protocols.
[0133] Example 9: Viscosity Using ASTM D562, viscosity (Stormer) was measured for flat and semi-gloss samples of Encor 471 and Encor 626 and compared to uncoalesced samples, TXMB, OE-400, K-FLEX® 850S, X-3411, X-3412, X-3413, a 1:1 ratio TXMB:OE-400 blend, and a 1:1 ratio benzyl alcohol:OE-400 blend. The results are shown in Figure 14 and are comparable for all coalescents and blends tested.
[0134] Example 10: Brightness ratio Using ASTM D2805, brightness ratios were measured for flat and semi-gloss samples of Encor 471 and Encor 626, comparing uncoalesced samples, TXMB, OE-400, K-FLEX® 850S, X-3411, X-3412, X-3413, a 1:1 ratio TXMB:OE-400 blend, and a 1:1 ratio benzyl alcohol:OE-400 blend. The results are shown in Figure 15 and are comparable for all coalescents and blends tested.
[0135] Example 11: Gloss Gloss was measured at 20, 60, and 85 degrees using ASTM D523 for flat and semi-gloss samples of Encor 471 and Encor 626, comparing uncored samples, TXMB, OE-400, K-FLEX® 850S, X-3411, X-3412, X-3413, a 1:1 ratio TXMB:OE-400 blend, and a 1:1 ratio benzyl alcohol:OE-400 blend. The results are shown in Figures 16, 17, and 18. The multifunctional additive blend of the present invention performed comparable to the high VOC TXMB in each coating, except for the Encor 471 semi-gloss formulation.
[0136] Example 12: Dust collection resistance Using the method described above, dirt pickup resistance was measured for flat and semi-gloss samples of Encor 471 and Encor 626 and compared to uncoalesced samples, TXMB, OE-400, K-FLEX® 850S, X-3411, X-3412, X-3413, a TXMB:OE-400 blend, and a 1:1 benzyl alcohol:OE-400 blend. The results are shown in Figure 19. The multifunctional additive blend of the present invention showed a significant performance improvement over the traditional low VOC coalescent, OE-400, in semi-gloss formulations.
[0137] Example 13: Printing Resistance Using ASTM D2064, print resistance was measured on flat and semi-gloss samples of Encor 471 and Encor 626, comparing uncored samples, TXMB, OE-400, K-FLEX® 850S, X-3411, X-3412, X-3413, a 1:1 ratio TXMB:OE-400 blend, and a 1:1 ratio benzyl alcohol:OE-400 blend. The results are shown in Figure 20 and are comparable for all coalescents and blends tested.
[0138] Example 14: Dry Adhesion Dry adhesion was measured using ASTM D3359B for flat and semi-gloss samples of Encor 471 and Encor 626, comparing uncored samples, TXMB, OE-400, K-FLEX® 850S, X-3411, X-3412, X-3413, a TXMB:OE-400 blend, and a 1:1 benzyl alcohol:OE-400 blend. The results are shown in Figure 22 and are comparable for all coalescents and blends tested.
[0139] Example 15: Drying Time Using ASTM D1640, dry times were measured for flat and semi-gloss samples of Encor 471 and Encor 626, comparing uncoalesced samples, TXMB, OE-400, K-FLEX® 850S, X-3411, X-3412, X-3413, a 1:1 ratio TXMB:OE-400 blend, and a 1:1 ratio benzyl alcohol:OE-400 blend. The results are shown in Figure 23 and are comparable for all coalescents and blends tested.
[0140] Example 16: Mudcracking Mud cracking from 14 to 60 mils was measured for Encor 471 and Encor 626 flat and semi-gloss samples at ambient temperature and 40° F. and compared to uncoalesced samples, TXMB, OE-400, K-FLEX® 850S, X-3411, X-3412, X-3413, a 1:1 ratio TXMB:OE-400 blend, and a 1:1 ratio benzyl alcohol:OE-400 blend. The results are shown in Figures 24 and 25 and are comparable for all coalescents and blends tested.
[0141] Example 17: Open Time Open times were measured for flat and semi-gloss samples of Encor 471 and Encor 626 and compared to uncoalesced samples, TXMB, OE-400, K-FLEX® 850S, X-3411, X-3412, X-3413, a 1:1 ratio TXMB:OE-400 blend, and a 1:1 ratio benzyl alcohol:OE-400 blend. The results are shown in Figure 26 and are comparable for all coalescents and blends tested.
[0142] [Example 18: Wet Edge] Wet edge measurements were taken on flat and semi-gloss samples of Encor 471 and Encor 626 and compared to uncored samples, TXMB, OE-400, K-FLEX® 850S, X-3411, X-3412, X-3413, a 1:1 ratio TXMB:OE-400 blend, and a 1:1 ratio benzyl alcohol:OE-400 blend. The results are shown in Figure 27 and are comparable for all coalescents and blends tested.
[0143] Example 19: Sag Resistance Using ASTM D4400 (4-24 mils), sag resistance was measured on flat and semi-gloss samples of Encor 471 and Encor 626, comparing uncored samples, TXMB, OE-400, K-FLEX® 850S, X-3411, X-3412, X-3413, a 1:1 ratio TXMB:OE-400 blend, and a 1:1 ratio benzyl alcohol:OE-400 blend. The results are shown in Figure 28 and are comparable for all coalescents and blends tested.
[0144] Example 20: Washability Using the method described above, washability was measured for flat and semi-gloss samples of Encor 471 and Encor 626 and compared to uncoalesced samples, TXMB, OE-400, K-FLEX 850S, X-3411, X-3412, X-3413, a 1:1 ratio TXMB:OE-400 blend, and a 1:1 ratio benzyl alcohol:OE-400 blend. A variety of soiling agents, both water-based and oil-based, were evaluated. Results are shown in Figures 29(a)-(h). Washability results for permanent markers are shown in Figure 30. Results are comparable for all coalescents and blends tested.
[0145] Example 21: (TXMB:Dibenzoate) Paint Evaluation / Testing Additional testing was performed using various ratios of TXMB:K-FLEX® 850S and TXMB:K-FLEX® 975P in various binders, namely Encor 471, EPS 2533, Acronal 296D (all styrene acrylics), as well as VSR 1050 and Encor 626 (both 100% acrylics), and Encor 379G (vinyl acrylic), in the paint formulations described below. The K-FLEX® coalescent selected for each paint sample was chosen based on the type of binder (850S for 100% acrylics, and 975P for vinyl acrylics and styrene-acrylic binders).
[0146] [Table 11]
[0147] [Contribution of VOCs] VOC calculations were performed to show the VOC contribution to various paint formulations with TXMB, OE-400, K-FLEX® 850S, or 975P (alone) depending on the binder as discussed above, and are shown in Figure 31 for (K-FLEX:TXMB) Blend 1, and (K-FLEX:TXMB) Blend 2. The specific K-FLEX® coalescent selected for each paint sample, whether used alone or in a blend, was chosen based on the type of binder (850S for 100% acrylic and vinyl acrylic binders, and 975P for styrene-acrylic binders).
[0148] The results show that formulations can be formulated down to 5 g / LVOC and still achieve good performance using the multifunctional additive blend of the present invention. This is surprising and runs counter to the conventional view that coalescents must have high VOCs to maintain performance.
[0149] [Scrub resistance] Scrub resistance was evaluated for three styrene-acrylic binders (Encor 471, EPS 2533, and Acronal 296D), two 100% acrylic binders (Encor 626 and VSR 1050), and one vinyl acrylic binder (Encor 379G), including TXMB, OE-400, K-FLEX® 850S, or 975P alone, as well as the inventive low VOC multi-functional additive blends of TXMB and 975P or 850S, as shown below. Encor 471:30:70 TXMB:975P, 70:30 TXMB:975P EPS 2533:30:70 TXMB:975P, 55:45 TXMB:975P Acronal 296D: 10:90 TXMB: 975P, 90:10 TXMB: 975P Encor 626:10:90 TXMB:850S, 90:10 TXMB:850S VSR 1050:40:60 TXMB:850S, 90:10 TXMB:850S Encor379G: 50:50 TXMB: 850S, 80:20 TXMB: 850S
[0150] The scrub resistance results are shown in Figures 32-37. The incorporation of higher VOC components and lower VOC dibenzoates (TXMB and dibenzoate, respectively, as listed above) resulted in coatings that were more scrub resistant than either TXMB or dibenzoate alone.
[0151] [Block resistance] Block resistance was measured on days 1 and 7 for the same binders and coalescents, as used previously in the scrub resistance evaluation, and the low-VOC multifunctional additive blends of the present invention. The results are shown in Figures 38-43. For most of the coatings tested, the high-VOC and low-VOC blends (TXMB and dibenzoate, respectively, as listed above) were able to equal the block resistance of the high-VOC control and even exceed the block performance of the dibenzoate alone.
[0152] [Gloss] Gloss was measured for the same binder and coalescent, and the inventive low VOC multi-functional additive blends of TXMB with K-FLEX® 850S and K-FLEX® 975P, as shown above. The results, shown in Figures 44-49 as gloss units, are comparable for all coalescents and blends tested.
[0153] [Dust absorption:] Dirt pickup resistance was measured for the same binder, coalescent, and low VOC multifunctional additive blends of the present invention as shown above in the scrub resistance test, with the exception of Acronal 296D, where only the 90:10 TXMB:975P blend was evaluated. The results are shown in Figures 50-55, with lower Δ%Y reflectance indicating greater dirt pickup resistance.
[0154] [Low temperature coalescence] Low temperature coalescence was measured for the same binder, coalescent, and low VOC multifunctional additive blends of the present invention as shown above in the scrub resistance test. The results are shown in Figures 56-61. The results obtained with the multifunctional additive blends evaluated were comparable to TXMB, OE-400, and K-FLEX® 850S or 975P alone.
[0155] Example 22: Direct Coatings on Metal - Wet Adhesion Test Wet adhesion testing using ASTM D3359 was performed on coated steel panels using the direct-to-metal waterborne coatings of Table 5 containing the inventive low-VOC multifunctional additive blends with propylene glycol dibenzoate and dipropylene glycol n-butyl ether as coalescent solvents or propylene glycol dibenzoate and benzyl alcohol as coalescent solvents. The left image in Figure 62 shows the results of wet adhesion testing (ASTM D3359) for the dibenzoate / ether combination. The right image in Figure 62 shows the results of wet adhesion testing for the dibenzoate / benzyl alcohol combination of the present invention, with the same formulation but with the ether replaced by benzyl alcohol. Figure 62 shows that benzyl alcohol in combination with dibenzoate provides a much improved wet adhesion over the dibenzoate / glycol ether combination typically used in direct-to-metal coatings.
[0156] Example 23: Direct Coating on Metal - Koenig Hardness Figure 63 shows Koenig hardness measurements over time for direct-to-metal waterborne coatings from Table 5, comparing a typical blend of propylene glycol dibenzoate and dipropylene glycol n-butyl ether; a low VOC multi-functional additive blend of the present invention with propylene glycol dibenzoate and benzyl alcohol; and a blend of butyl benzyl phthalate and dipropylene glycol n-butyl ether (DPnB) (all in a 1:1 ratio). The results show that the multi-functional additive of the present invention combining benzyl alcohol with dibenzoate gives better initial hardness measurements in direct-to-metal coatings than the traditional glycol ethers used with dibenzoate or phthalate.
[0157] Example 24: Direct Coating on Metal - Flash Rust Table 6 shows the visual ratings for flash rust using the flash rust test method described above. The results reflect that sodium benzoate (NaB) demonstrated compatibility with propylene glycol dibenzoate (PGDB) and benzyl alcohol in direct-to-metal coatings (Table 5), thereby eliminating flash rust formation. The combination of all three provided improvements in wet adhesion, initial hardness, and flash rust resistance (all results not shown).
[0158] [Table 12]
[0159] Example 25: Additional Tests - Direct Coating to Metal Additional testing was performed on the 40 PVC white direct to metal primer formulation described below, similar to that in Table 5, except that sodium benzoate was incorporated rather than benzoic acid for corrosion (flash rust) resistance. The testing compared the use of a multi-functional additive blend of the present invention containing PGDB and K-FLEX® 850S, each in combination with benzyl alcohol (1:1 ratio), to a blend containing K-FLEX® PG (PGDB) and butyl benzyl phthalate (BBP), each in combination with DPnB (1:1 ratio).
[0160] [Table 13]
[0161] The results, as seen in Figure 64, show that samples containing the inventive blend with benzyl alcohol achieved greater initial hardness development than samples containing the blend with DPnB. In addition, after 18 hours of drying, the samples containing the inventive multi-functional additive blend with benzyl alcohol had higher block ratings than the other samples at room temperature (23°C) (Figure 65). After 7 days, all samples had excellent block ratings. For block resistance at 50°C, samples containing the inventive multi-functional additive blend with benzyl alcohol had higher block ratings at both 7 and 14 days (Figure 66).
[0162] The same samples were also evaluated for dry and wet adhesion. The paint films were allowed to dry on steel panels for 21 days, immersed in water for 1 hour, and then tested immediately. Samples containing the multifunctional additive blend of the present invention with benzyl alcohol had similar wet and dry adhesion compared to BBP:DPnB. Samples with K-FLEX® PG:DPnB had very poor wet adhesion. The results are shown in Figure 67.
[0163] Example 26: Freeze-thaw test Freeze-thaw tests were performed on styrene acrylic binders and all acrylic binders comparing TXMB, TEGDO, K-FLEX® 850S, X-3411, and X-3413. Results for the styrene-acrylic binder based coatings are shown in Figure 68. Results for TXMB are not shown because it gelled during the freeze-thaw cycles. The other coalescents performed similarly after three freeze-thaw cycles, with TEGDO increasing in viscosity by 6 KU compared to 4 KU for X-3413. In the all acrylic binder formulations, coatings with 850S, TEGDO, and TXMB experienced a viscosity increase of over 5 KU after the first three freeze-thaw cycles (Figure 69). The largest increase in viscosity was observed with the 850S sample, with an increase of almost 30 KU, followed by TEGDO with an increase of 12.5 KU. Notably, coating with X-3411 or X-3413 for each of the different binders had minimal change in viscosity. Additionally, the inclusion of benzyl alcohol or high VOC ingredients (X-3411 and X-3413) dramatically improved stability compared to 850S alone, as will be discussed further in Example 27.
[0164] Example 27: Efficacy of higher VOC components / polymer stability in multifunctional additive blends. A few grams of benzyl alcohol alone was added to Encor 471 styrene-acrylic polymer. The polymer was observed to be completely destabilized. The amount added was much less than the percentage of benzyl alcohol in the benzyl alcohol:850S (X-3411) blend previously tested. In the above example, the benzyl alcohol:850S blend (1:1 ratio) was added, but did not destabilize the polymer. When added alone, benzyl alcohol had a significant polymer destabilizing effect. The same effect was observed in the case of Encor 626 acrylic binder as well. When benzyl alcohol was added alone, even in small amounts, polymer flakes precipitated out of the binder, indicating destabilization. When the benzyl alcohol:850S blend was added, this did not occur. The binder (polymer) remained stable. The percentage of benzyl alcohol in the multifunctional additive blend was 1.25% by weight of the binder. In contrast, the use of benzyl alcohol alone, even in amounts as low as 1.1 wt %, or even 0.5 wt %, destabilized the binder.
[0165] The inventive multifunctional additive blend of benzyl alcohol:dibenzoate (850S) improved the incorporation of benzyl alcohol into the polymer emulsion, allowing for a much more stable product. The same was observed with benzyl alcohol blended with OE-400.
[0166] Some of the observed results are presented in Figures 70-73. Figure 70 shows an image of Encor 626 binder blended with 2.5 wt% of the low VOC multifunctional additive blend of the present invention, X-3411, to the binder. The image shows a stable polymer emulsion resulting from the incorporation of the low VOC multifunctional additive. Figure 71 shows an image of Encor 626 binder blended with 1.1 wt% benzyl alcohol to the binder. The image shows an unstable polymer emulsion, with aggregates / flocculants observed at the bottom of the glass jar. Figure 72 shows an image of a fully formulated coating of Encor 471, semi-gloss, with post-addition of benzyl alcohol to the binder at 3.95 wt%. As can be seen in the image, aggregates and flocculants were observed. When 7.9 wt% X-3411 was used on the binder, the same level of benzyl alcohol (3.95 wt% on the binder) was achieved, yet surprisingly, a stable, non-flocculating coating was obtained, as shown in the drawdown on the right side of FIG. 73.
[0167] Example 28: Low VOC Multifunctional Additive Blend - Ratio The preceding examples demonstrate the effectiveness of the low VOC multifunctional additive blends of the present invention, which contain various ratios of low and high volatility components. The low VOC multifunctional additive blends of the present invention contain at least one low volatility component and at least one volatile component, and are combined in a ratio of low volatility to high volatility components of about 1:10 to about 10:1. The low volatility components are: dibenzoates, blends of dibenzoates, monobenzoates, phthalates, terephthalates, 1,2-cyclohexanedicarboxylate esters, citrates, adipates, triethylene glycol dioctanoates (TEGDO), Optifilm™ Enhancer 400, or a mixture of purified diisobutyl esters of adipic, glutaric, and succinic acids (Coasol). The high volatility components are: diethylene glycol monomethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (TXMB), benzylamine, phenoxyethanol, phenylethanol, benzyl alcohol, benzyl benzoate, butyl benzoate, 3-phenylpropanol, 2-methyl-3-phenylpropanol, β-methylcinnamyl alcohol, or vanillin. The previously reported combinations of TXMB and TEGDO, or TXMB and OE-400, are not included in the low VOC multifunctional additive blend of the present invention.
[0168] The low volatility and high volatility components are blended in a ratio of 1:10 to 10:1 to form the low VOC multifunctional additive of the present invention, and in addition to coalescence, improvements in hardness, hardness development, scrub resistance, block resistance, dirt pickup resistance, wet adhesion, and in some cases flash rust resistance (when combined with benzoic acid according to the methods referenced herein) are obtained. The low VOC multifunctional additive of the present invention is an alternative to the traditional higher VOC coalescent agents used heretofore, and a way to achieve improved performance while lowering the VOC content of coatings and other aqueous polymeric film-forming compositions.
[0169] Example 29: Carriers for pigments and colorants The low VOC multifunctional additive blend of the present invention is a useful carrier for water-based or solvent-based pigments or colorants. Typical formulations for water-based and solvent-based colorants using X-3411 are shown below, but the amount of low VOC multifunctional additive blend in this application will vary depending on the water-based polymer system, the nature and type of pigment and colorant, the color strength required, the presence of other ingredients, and the presence of other solvents relative to the water.
[0170] [Table 14]
[0171] [Table 15]
[0172] The above examples show that low VOC coatings can be formulated with less volatile coalescent components (such as, but not limited to, dibenzoate glycol esters, monobenzoates, phthalates, and other low VOC coalescents) to have, in addition to coalescence, high hardness, block resistance, gloss, dirt pick-up resistance, scrub resistance, wet adhesion, and corrosion resistance, among other properties, by blending the low volatility components with the high volatility components in accordance with the present invention. Significant improvements in various performance properties are achieved with minimal increase in VOC content. The use of known low volatility coalescents or film formers in combination with the high volatility components of the present invention gives formulators the freedom to design their coatings to include higher VOC components to achieve various performance properties that are critical to certain applications without unduly increasing the VOC content of the formulation. The present invention demonstrates that known low VOC coalescents or film-formers can be used in combination with higher VOC components, some of which are unknown or have never been previously recognized or used as coalescents, to improve properties that in the past had to be compromised by the use of the lower VOC coalescent components. Surprisingly, the multifunctional additive blends of the present invention provide not only coalescence, but also improved performance over that achieved with the high VOC coalescents used alone.
[0173] Although the examples have focused only on some of the available lower VOC coalescent components and some of the basic binders (coating compositions) for purposes of illustrating the properties of the coalescent polymers, the improvements achieved are expected to apply to a variety of low VOC coalescent components, polymers (binders), and pigment volume concentrates. Unexpectedly, formulations using the high volatility components identified herein (which may not have been previously known or used as coalescent agents) and lower VOC components achieved improvements in hardness, hardness development, block resistance, scrub resistance, dirt pickup resistance, wet adhesion, corrosion resistance, and polymer stabilization, among other properties, in the coatings evaluated.
[0174] The low VOC multifunctional additive blend of the present invention is a viable alternative for use in coatings or other water-based polymer systems where low VOC content is desired. The low VOC multifunctional additive blend of the present invention actually improves important properties of coatings and other water-based systems while providing low VOC content. The low VOC multifunctional additive blend is also useful for dispersing colorants prior to addition to water-based polymer systems.
[0175] While in accordance with the patent statutes, the best mode and preferred embodiments have been set forth, the scope of the invention is not limited thereto, but rather by the scope of the appended claims.
Claims
1. 1. A low VOC multifunctional additive blend for use in water-based or solvent-based polymeric film-forming compositions, comprising: a. at least one low volatility component selected from dibenzoates, blends of dibenzoates, monobenzoate esters, phthalates, terephthalates, 1,2-cyclohexanedicarboxylate esters, citrates, adipates, triethylene glycol dioctanoate, triethylene glycol bis(ethylhexanoate-2), and mixtures of purified diisobutyl esters of adipic acid, glutaric acid, and succinic acid; of b. at least one highly volatile component selected from benzylamine, phenoxyethanol, phenylethanol, benzyl alcohol, 3-phenylpropanol, 2-methyl-3-phenylpropanol, β-methylcinnamyl alcohol, and vanillin; Including blends with A low VOC multifunctional additive blend, wherein the weight ratio of said high volatility component to said low volatility component in said low VOC multifunctional additive blend is from 10:1 to 1:
10.
2. 2. The low VOC multifunctional additive blend of claim 1, wherein the at least one high volatility component is selected from the group consisting of benzyl alcohol, 3-phenylpropanol, 2-methyl-3-phenylpropanol, β-methylcinnamyl alcohol, and vanillin.
3. the dibenzoate is selected from the group consisting of diethylene glycol dibenzoate, dipropylene glycol dibenzoate, 1,2-propylene glycol dibenzoate, triethylene glycol dibenzoate, tripropylene glycol dibenzoate, and mixtures thereof; the monobenzoate ester is selected from the group consisting of 2-ethylhexyl benzoate, isodecyl benzoate, isononyl benzoate, 3-phenylpropyl benzoate, 2-methyl-3-phenylpropyl benzoate, and mixtures thereof; the terephthalate is selected from the group consisting of di-2-ethylhexyl terephthalate, dibutyl terephthalate, diisopentyl terephthalate, and mixtures thereof; the 1,2-cyclohexanedicarboxylate ester is diisononyl-1,2-cyclohexanedicarboxylate; the phthalate is selected from the group consisting of di-n-butyl phthalate, diisobutyl phthalate, butyl benzyl phthalate, and mixtures thereof; and 2. The low VOC multifunctional additive blend of claim 1, wherein said citrate is selected from the group consisting of acetyl tributyl citrate, tri-n-butyl citrate, and mixtures thereof.
4. 10. The low VOC multifunctional additive blend of claim 1, wherein said low volatility component is a dibenzoate or a blend of dibenzoates.
5. 5. The low VOC multifunctional additive blend of claim 4, wherein said dibenzoate or blend of dibenzoates comprises propylene glycol dibenzoate.
6. 2. The low VOC multifunctional additive blend of claim 1, wherein said low volatility component is triethylene glycol dioctanoate or triethylene glycol bis(ethylhexanoate-2).
7. The low VOC multifunctional additive blend of any one of claims 1 to 6, wherein the highly volatile component is benzyl alcohol.
8. 8. The low VOC multifunctional additive blend of claim 7 further comprising benzoic acid or a salt thereof.
9. The low VOC multifunctional additive blend of any one of claims 1 to 8, further comprising a colorant.
10. 2. The low VOC multifunctional additive blend of claim 1 comprising benzyl alcohol and triethylene glycol dioctanoate, wherein the weight ratio of benzyl alcohol to triethylene glycol dioctanoate is 1:
1.
11. a benzyl alcohol and dibenzoate blend, wherein the weight ratio of benzyl alcohol to dibenzoate blend is from 1:1 to 1:3; or Benzyl alcohol and triethylene glycol bis(ethylhexanoate-2), where the weight ratio of benzyl alcohol to triethylene glycol bis(ethylhexanoate-2) is 1:
1. comprising 2. The low VOC multifunctional additive blend of claim 1, wherein the dibenzoate blend comprises a mixture of diethylene glycol dibenzoate and dipropylene glycol dibenzoate, or a mixture of diethylene glycol dibenzoate, dipropylene glycol dibenzoate, and 1,2-propylene glycol dibenzoate.
12. 12. A water-based or solvent-based polymeric film-forming composition comprising the low-VOC multifunctional additive blend of any one of claims 1 to 11.
13. 13. The aqueous or solvent borne polymeric film forming composition of claim 12 comprising a styrene-acrylic binder, a vinyl acrylic binder, an acrylic binder, a vinyl acetate-ethylene binder, or an alkyd binder.
14. a binder selected from vinyl polymers, polyurethanes, polyamides, polysulfides, nitrocellulose and other cellulosic polymers, polyvinyl acetates and their copolymers, polyacrylates and their copolymers, acrylic resins and their copolymers, epoxies, phenol-formaldehyde polymers, melamine resins, alkyd resins, and vinyl ester resins of versatic acid; Pigments, Surfactants, and Rheology Modifiers Further comprising: The low VOC multi-functional additive blend is present in an amount of 0.1 to 15% by weight of the binder, based on 100 grams of binder.
13. The aqueous or solvent-borne polymeric film-forming composition of claim 12.
15. Pigments, Dispersants, and Water or solvent 13. The aqueous or solvent-based polymeric film forming composition of claim 12 further comprising:
16. A direct-to-metal polymeric film-forming composition comprising the low-VOC multifunctional additive blend of any one of claims 1 to 11.
17. 1. A method for improving the properties of an aqueous polymeric film forming composition, comprising: at least one low volatility component selected from dibenzoates, blends of dibenzoates, monobenzoate esters, phthalates, terephthalates, 1,2-cyclohexanedicarboxylate esters, citrates, adipates, triethylene glycol dioctanoate, triethylene glycol bis(ethylhexanoate-2), and mixtures of purified diisobutyl esters of adipic acid, glutaric acid, and succinic acid; adding at least one highly volatile component selected from benzylamine, phenoxyethanol, phenylethanol, benzyl alcohol, 3-phenylpropanol, 2-methyl-3-phenylpropanol, β-methylcinnamyl alcohol, and vanillin to form a low VOC multifunctional additive blend; and adding said low VOC multifunctional additive blend to an aqueous polymeric film-forming composition; the weight ratio of the high volatility component to the low volatility component in the low VOC multifunctional additive blend is from 10:1 to 1:10; The method wherein the improved property is one or more properties selected from compatibility with binders, wet adhesion, hardness, scrub resistance, block resistance, freeze-thaw, dirt pickup resistance, corrosion (flash rust) resistance, antibacterial properties, and total VOC content.
18. 20. The method of claim 17, further comprising dispersing a colorant in said low VOC multifunctional additive blend prior to being added to the aqueous polymeric film-forming composition.
19. 20. The method of claim 17, wherein the low-VOC multifunctional additive blend comprises a dibenzoate, further comprising the step of synthesizing the dibenzoate in a percent molar excess of benzoic acid in the range of 1% to 30% in the reaction to form an acid excess dibenzoate.
20. 20. The method of claim 17, wherein the low-VOC multifunctional additive blend comprises a dibenzoate or a blend of dibenzoates, further comprising dissolving benzoic acid or a salt thereof in the dibenzoate or blend of dibenzoates.
21. 21. The method of claim 19 or 20, wherein the at least one high volatility component of the low VOC multifunctional additive blend is benzyl alcohol.
22. 18. The method of claim 17, wherein the at least one highly volatile component is selected from the group consisting of benzyl alcohol, 3-phenylpropanol, 2-methyl-3-phenylpropanol, β-methylcinnamyl alcohol, and vanillin.
23. 12. Use of the low VOC multifunctional additive blend according to any one of claims 1 to 11 in water-based or solvent-based polymeric film forming compositions for architectural coatings, industrial coatings, OEM coatings, interior and exterior paints, coatings on metals, direct to metal coatings, marine coatings, film coatings, vinyl film compositions, wood coatings, wood treatments, paper coatings, fabric coatings, textile coatings, wallpaper coatings, decorative coatings, structural coatings, cement coatings, concrete coatings, floor coatings, varnishes, inks, graphic inks, water-based stains, solvent-based stains, adhesive compositions, glues, sealants, or caulkings.
Citation Information
Patent Citations
Waterrreducing resin composition
JP1981079148A
Coating latex with lowered blushing properties
JP1991131674A
Anticorrosive water-based coating composition
JP1996073776A
Aqueous film-forming composition with reduced volatile organic compound content
JP2010508420A
Low-VOC additives for extending the wet edge and open time of water-based coatings.
JP2012502138A